Endothermic reaction of feed gas by resistance heating

By using a combination of the macrostructure of conductive materials in the catalyst and the ceramic coated catalytic active material, the problem of low heat transfer efficiency is solved, and the efficiency of endothermic reactions and energy consumption are improved.

CN114786810BActive Publication Date: 2025-04-18HALDOR TOPSOE AS +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080084547.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2020-12-03
Publication Date
2025-04-18
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

The prior art has low heat transfer efficiency in the catalyst bed reaction zone, resulting in limited endothermic reaction efficiency, especially in steam reforming equipment, where the heat transfer rate limits the reaction rate.

Method used

The macrostructure of conductive materials is used as a structural catalyst to form a composite material through uniform mixing of conductive metal materials and ceramic materials, increasing the resistivity of the material to increase the heat flux, and optimizing the endothermic reaction through specific macrostructure design and ceramic coating supported by the ceramic coating.

Benefits of technology

By increasing the heat flux and optimizing the catalyst structure, the efficiency of the endothermic reaction is significantly improved, the number of catalysts and the size of the reactor system is reduced, while energy consumption and emissions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114786810B_ABST
    Figure CN114786810B_ABST
Patent Text Reader

Abstract

A structured catalyst is arranged for catalyzing an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of an electrically conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material, wherein the electrically conductive material is at least partially a composite material in the form of a homogeneous mixture of an electrically conductive metallic material and a ceramic material, wherein the macrostructure is at least partially composed of two or more materials having different resistivities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a structured catalyst for carrying out an endothermic reaction of a raw gas, wherein the structured catalyst comprises a macrostructure of a first conductive material, the macrostructure supports a ceramic coating, and the ceramic coating supports a catalytically active material. Background of the Invention

[0003] Endothermic reactions are often challenged by the efficiency of heat transfer across the catalyst bed reaction zone within the reactor unit. Conventional heat transfer via convection, conduction, and / or radiant heating can be slow and often encounters large resistances in many configurations. This challenge can be illustrated with the tubular reformer in a steam reforming plant, which can effectively be viewed as a large heat exchanger with heat transfer as the rate limiting step. Due to the heat transfer rate through the tube walls and the catalyst within the tubes and due to the endothermic nature of the steam reforming reaction, the temperature on the innermost side of the tubes of a tubular reformer is slightly lower than the temperature on the outside of the tubes.

[0004] A method of supplying heat inside the catalyst instead of in the jacket of the catalyst is by resistance heating. DE102013226126 describes a temperature-variable methane reforming process with energy recovery, in which methane is reformed by carbon dioxide into a synthesis gas consisting of carbon monoxide and hydrogen. The starting gases CH4 and CO2 are led to a fixed bed reactor consisting of conductive and catalytic particles, which are electrically heated to a temperature of about 1000 K. The conversion of the reaction gases and the heat of the generated synthesis gas take place in the fixed bed reactor.

[0005] It is an object of the present invention to provide an alternative configuration of an electrically heated structured catalyst and reactor system for carrying out an endothermic reaction of a feed gas.

[0006] It is also an object of the present invention to provide a structured catalyst and reactor system with integrated heat and catalyst supply.

[0007] Another object of the present invention is to provide a structured catalyst and reactor system for endothermic reaction of feed gas containing hydrocarbon compounds, wherein the total energy consumption is reduced compared to systems with externally heated reactors, such as side-fired or top-fired steam methane reformers (SMRs), which provide a reference for industrial-scale steam reforming. By using electrical heating, the high flue gas temperature of the fired SMR is avoided, and therefore, less energy is required in the reforming part of the electrically heated reactor.

[0008] Another object of the present invention is to provide a structured catalyst and reactor system for carrying out an endothermic reaction of a feed gas, for example a feed gas containing hydrocarbon compounds, wherein the amount of catalyst and the size of the reactor system are reduced compared to conventional reactors for carrying out endothermic reactions. Furthermore, the present invention provides the possibility of tailoring, thereby reducing the amount of catalytically active material, while having a controlled reaction front of the reaction.

[0009] Furthermore, it is an object of the present invention to provide a method for producing a product gas from an endothermic reaction of a feed gas (e.g., a feed gas containing hydrocarbon compounds), wherein the product gas output from the reactor system has a relatively high temperature and a relatively high pressure. In particular, it is desirable if the temperature of the product gas output from the reactor system is between about 900° C. and 1100° C. or even up to 1300° C., and if the pressure of the product gas output from the reactor system is between about 30 bar and about 100 bar. The present invention allows precise control of the temperature of the product gas output from the reactor system.

[0010] One advantage of the present invention is that overall emissions of carbon dioxide and other emissions harmful to the climate can be significantly reduced, particularly when the electricity used in the reactor system comes from renewable energy sources. SUMMARY OF THE INVENTION

[0012] The present invention relates to a structured catalyst arranged for catalyzing an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of an electrically conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material, wherein the electrically conductive material is at least partially a composite material in the form of a homogeneous mixture of an electrically conductive metallic material and a ceramic material, wherein the macrostructure is at least partially composed of two or more materials having different resistivities.

[0013] The present invention is directed to improving structured catalysts of the type comprising macrostructures of electrically conductive material, wherein the macrostructures carry a ceramic coating, and wherein the ceramic coating carries a catalytically active material.

[0014] The present invention is based on the discovery that for structured catalysts of the type described, the conductive material in the form of a homogeneous mixture of conductive metallic material and ceramic material can be made to have a selected level of resistivity, and that by using a conductive material with increased resistivity, the heat flux through the material can be increased. The present invention has demonstrated that by applying a structured catalyst with a higher resistivity achieved by a composite material, an increased cross section of the structured catalyst can be used, which offers the possibility of reducing the number of structured catalysts required. This in turn reduces the number of monolith bridges required and therefore reduces the number of connections required to build the array of the present invention.

[0015] The present invention is also based on the recognition that when using conductive materials in the form of composite materials as described above, it is possible to create structured catalysts with different resistivities, thereby creating a heat flux in the direction of the feed gas flowing through the catalyst. Such a design in turn allows for optimization of the endothermic reactions occurring in the catalyst to achieve a more efficient reaction.

[0016] The present invention also relates to a reactor system for carrying out an endothermic reaction of a raw gas, the reactor system comprising:

[0017] a) the catalyst of the present invention;

[0018] b) a pressure-resistant shell containing the catalyst, the pressure-resistant shell comprising an inlet for inputting the feed gas and an outlet for outputting the product gas, wherein the inlet is located so that the feed gas enters the catalyst at a first end and the product gas leaves the catalyst from a second end; and

[0019] c) A heat insulation layer between the structured catalyst and the pressure-resistant shell.

[0020] The invention also relates to the use of a catalyst according to the invention or a reactor system according to the invention, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide formation, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0021] definition

[0022] With respect to the present invention, the terms discussed below have the following meanings:

[0023] The term "monolith" refers to a coherent structure having a well-defined surface area, wherein "coherent" refers to the continuous phase.

[0024] The term "sintering process" refers to the process of compacting and forming a solid mass of material, including heating at least a portion of the material to make it moldable or spreadable without melting the material to the liquid point, and then cooling the material to solidify into its final form.

[0025] The term "hot spot" refers to a point of an electrically conductive structured catalyst material where the material has become highly heated due to the transfer of electrical energy to that point due to a local high current density, which greatly exceeds the energy required to drive the chemical reaction near that point, and where there is a risk of damage to the material due to heating of the material to a temperature close to its melting point.

[0026] The term "resistivity" of a material refers to the resistivity measured by a method comprising the steps of passing a fixed current through the material, measuring the potential difference across the material, and correlating the resistivity according to Ohm's law. Alternatively, other conventional methods known in the art may be used.

[0027] The term "at the first end" with respect to a connecting bridge on a monolith refers to a location on the monolith closer to the first end than the second end. The term "at the second end" with respect to a connecting bridge on a monolith refers to a location on the monolith closer to the second end than the first end.

[0028] The term "monolithic bridge" refers to a bridge connecting two monoliths, wherein the bridge is a coherent structure, wherein "coherent" refers to a continuous phase.

[0029] The term "composite material in the form of a homogeneous mixture" refers to a mixture whose components are in the same proportions throughout any given sample of the mixture.

[0030] The term "non-composite conductive metal material" refers to a conductive metal material that does not contain a ceramic material.

[0031] The term "moldable state" refers to a material being in a formable state that allows the material to adhere to and / or bond with another material in the same state.

[0032] The term "electric current" includes direct current and alternating current.

[0033] The term "green body" refers to a weakly bound moldable material, such as in the form of a bound powder, prior to sintering or oxidation.

[0034] The term "consisting of a plurality of chemical elements" means at least one chemical element.

[0035] Furthermore, the term "steam reforming" is intended to mean a reforming reaction according to one or more of the following reactions:

[0036]

[0037]

[0038]

[0039] Reactions (i) and (ii) are steam methane reforming reactions, while reaction (iii) is a dry methane reforming reaction.

[0040] For higher hydrocarbon compounds, namely C n H m , where n ≥ 2, m ≥ 4, equation (i) can be summarized as:

[0041]

[0042] Where n≥2, m≥4.

[0043] Typically, steam reforming is accompanied by the water-gas shift reaction (v):

[0044]

[0045] The term "steam methane reforming" is meant to include reactions (i) and (ii), the term "steam reforming" is meant to include reactions (i), (ii) and (iv), and the term "methanation" includes the reverse reaction of reaction (i). In most cases, all of these reactions (i)-(v) are at or near equilibrium at the reactor system outlet.

[0046] The term "pre-reforming" is generally used to include the catalytic conversion of higher hydrocarbon compounds according to reaction (iv). Pre-reforming is usually accompanied by steam reforming and / or methanation (depending on the gas composition and operating conditions) and water gas shift reaction. Pre-reforming is usually carried out in an adiabatic reactor, but it is also possible to carry out in a heated reactor.

[0047] The term "hydrogen cyanide synthesis" refers to the following reaction:

[0048]

[0049]

[0050] The term "dehydrogenation" is intended to mean the following reaction:

[0051]

[0052] Wherein R1 and R2 can be any appropriate groups in the hydrocarbon compound molecule, such as -H, -CH3, -CH2 or -CH.

[0053] The term "methanol cracking" is intended to denote the following reaction:

[0054]

[0055]

[0056] Typically, the methanol cracking reaction is accompanied by a water-gas shift reaction (v).

[0057] The term "ammonia cracking" is intended to denote the following reaction:

[0058] DETAILED DESCRIPTION OF THE INVENTION

[0060] The structured catalyst of the composite material of the present invention

[0061] The present invention further relates to a structured catalyst arranged for catalyzing an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of an electrically conductive material, the macrostructure carrying a ceramic coating, wherein the ceramic coating carries a catalytically active material, wherein the electrically conductive material is at least partially a composite material of an electrically conductive metallic material and a ceramic material, wherein the macrostructure is at least partially composed of two or more materials having different resistivities.

[0062] In certain embodiments, the macrostructure consists at least in part of one or more composite materials and one or more non-composite conductive metal materials. In certain embodiments, the macrostructure consists at least in part of two composite materials and one non-composite conductive metal material. In certain embodiments, the macrostructure consists at least in part of two or more composite materials.

[0063] The conductive metal material of the composite material can be any conventional catalytically active metal material. In a specific embodiment of the structured catalyst of the present invention, the metal material is an alloy comprising one or more substances selected from Fe, Cr, Al, Co, Ni, Zr, Cu, Ti, Mn and Si.

[0064] In a particular embodiment, the material of the macrostructure is selected from an alloy comprising iron and chromium, an alloy comprising iron, chromium and aluminum, an alloy comprising iron and cobalt, and an alloy comprising iron, aluminum, nickel and cobalt. In a particular embodiment, the material of the macrostructure is a so-called "Alcoal", which is a specific type of alloy comprising iron, aluminum, nickel and cobalt, and optionally copper, titanium. In a particular embodiment, the material of the macrostructure is a FeCr alloy comprising iron, chromium and aluminum. In a particular embodiment, the material of the macrostructure is an alloy "Kanthal" comprising iron, chromium and aluminum oxide.

[0065] Due to its electrical resistance properties, "Kanthal" has proven to be a good choice for macrostructural materials.

[0066] The ceramic material of the composite material can be any conventional ceramic material. In a specific embodiment of the structured catalyst of the present invention, the ceramic material is an oxide of a substance selected from Al, Mg, Ce, Zr, Ca, Y and La. In a specific embodiment of the structured catalyst of the present invention, the ceramic material is selected from any of Al2O3, ZrO2, MgAl2O3, CaAl2O3, any combination thereof, and any of the materials and combinations mixed with oxides of Y, Ti, La or Ce. In a specific embodiment of the structured catalyst of the present invention, the ceramic material is selected from Al2O3, ZrO2, MgAl2O3, CaAl2O3, and any combination thereof. Ceramic oxides have low electrical conductivity and therefore have insulating properties. When added to a conductive metal material, the ceramic oxide will increase the resistivity of the resulting composite material.

[0067] In a particular embodiment of the structured catalyst of the present invention, the ratio of metal material to ceramic material based on the weight in the macrostructure is in the range of 50 to 1, preferably 40 to 1, more preferably 30 to 2, more preferably 24 to 3 and most preferably 19 to 4.

[0068] In a specific embodiment of the structured catalyst of the present invention, the structured catalyst is in the form of at least one monolith, wherein a plurality of flow channels are formed in the monolith for transporting the feed gas from a first end where the feed gas enters through the monolith to a second end where the product gas leaves, wherein the monolith has a longitudinal axis extending from the first end to the second end.

[0069] In a specific embodiment of the structured catalyst of the present invention, the macrostructure of the monolith is composed of two or more composite materials with different compositions in the direction of the longitudinal axis to provide different resistivities. In a specific embodiment of the structured catalyst of the present invention, the macrostructure of the monolith is composed of at least three composite materials, preferably at least four composite materials, more preferably at least five composite materials, more preferably at least six composite materials, more preferably at least seven composite materials, and most preferably at least eight composite materials. In a specific embodiment of the structured catalyst of the present invention, the macrostructure of the monolith includes at least the first, second and third composite materials in the direction from the first end to the second end, wherein the second composite material has a higher resistivity compared to the first and third composite materials, the third composite material has a lower resistivity compared to the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second and third composite materials. This design provides a structured catalyst with different heat fluxes, which can be related to the chemical reaction in the channel. Having a low heat flux in the first part of the monolith allows the heat supplied to be balanced with the chemical reaction rate, because the reaction rate at the first end is lower due to the lower temperature at the first end. As the temperature increases as the gas in the channel travels toward the second end, having a higher heat flux is an advantage because the chemical reaction rate in this area is also higher and more reactants can be consumed. At the second end of the monolith, having a low heat flux again can be an advantage because the highest temperatures are reached at this end and it is easier to control the temperature to the desired operating set point if the heat flux in this section is low.

[0070] In a specific embodiment of the structured catalyst of the present invention, the macrostructure of the monolith is composed of one or more composite materials and non-composite conductive metal materials having different compositions in the direction of the longitudinal axis to provide different resistivities.

[0071] In a specific embodiment of the structured catalyst of the present invention, the macroscopic structure of the monolith is composed of two or more, preferably three or more, more preferably four or more, more preferably five or more, more preferably six or more composite materials and non-composite conductive metal materials with different compositions in the direction of the longitudinal axis to provide different resistivities.

[0072] Preferably, the macrostructure of the monolith includes at least the first and second composite materials and a non-composite conductive metal material in the direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first composite material and the non-composite material, the non-composite material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second composite material and the resistivity of the non-composite material. The technical advantages of this design are the same as those described in the previous paragraph. The described embodiment of the structured catalyst is suitable for use in the array of the present invention, see below. In this array, the monolith bridge conductive material is preferably a non-composite conductive metal material, such as the same non-composite material used in the macrostructure.

[0073] Different resistivities of the composite material can be obtained by varying one or more parameters selected from: a) the ratio of conductive metallic material to ceramic material, b) the size of the ceramic particles, c) the shape of the ceramic particles, and d) the type of ceramic material.

[0074] In a particular embodiment of the structured catalyst of the present invention, a monolith composed of two or more composite materials having different compositions is prepared by a process comprising the following steps:

[0075] Prepare a plurality of slurries, the slurries comprising:

[0076] at least one first slurry having a first composition, wherein the first slurry comprises a metal powder having a first alloy composition, a ceramic powder and a first binder,

[0077] and at least one second slurry having a second composition, wherein the second slurry (10b) comprises a metal powder having a second alloy composition and a second binder

[0078] wherein the first alloy composition and the second alloy composition each consist of a plurality of chemical elements, and wherein the chemical elements are selected such that, for each chemical element present in an amount greater than 0.5% by weight of the respective alloy composition, the chemical element is contained in both the first and second alloy compositions, and

[0079] o for a chemical element present in an amount of up to 5.0 weight percent in the first alloy composition, the amount of the chemical element differs between the first alloy composition and the second alloy composition by up to 1 percentage point, and

[0080] o For a chemical element present in the first alloy composition in an amount greater than 5.0 weight percent, the amount of the chemical element differs between the first alloy composition and the second alloy composition by at most 3 percentage points, and

[0081] Transfer multiple slurries into the supply room of the processing equipment,

[0082] forming a green body from the plurality of slurries by forcing the slurries from a supply chamber through a die of a processing device, and

[0083] sintering or oxidizing the green body to obtain a composite component having a varying resistivity (ρ) along a longitudinal direction of the composite component, the longitudinal direction corresponding to the direction of movement of the slurry through the die, and a varying resistivity (ρ) resulting from the first composition being different from the second composition.

[0084] In a particular embodiment of the structured catalyst of the invention, the catalyst is an array of the invention.

[0085] The present invention further relates to a structured catalyst arranged for catalyzing an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of an electrically conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material, wherein the electrically conductive material is a composite material in the form of a homogeneous mixture of an electrically conductive metal material and a ceramic material.

[0086] Catalyst array of the present invention

[0087] In the present application, the expression "the array of the present invention" refers to the "catalyst array of the present invention", and the two expressions can be used interchangeably.

[0088] The present invention further relates to an array comprising the first and second structured catalysts of the present invention, wherein:

[0089] a) the first and second structured catalysts are in the form of first and second monoliths, respectively;

[0090] b) the first and second monoliths each have a plurality of flow channels formed therein for conveying the feed gas through the monolith from a first end where the feed gas enters to a second end where the product gas exits, wherein the first and second monoliths each have a longitudinal axis extending from the first end to the second end;

[0091] c) an array comprising at least first and second conductors electrically connected to the first and second monoliths, respectively, and to a power source, wherein the power source is dimensioned to heat at least a portion of the first and second monoliths to a temperature of at least 500° C. by passing an electric current through the macrostructure, wherein the first conductor is electrically connected directly or indirectly to the first monolith, and the second conductor is electrically connected directly or indirectly to the second monolith, and wherein the conductors are connected at a location on the array closer to the first end than to the second end,

[0092] d) the first and second monoliths are electrically connected via a monolith bridge of a monolith bridge conductive material,

[0093] e) the array is configured to direct current from the first conductor through the first monolith to the second end, then through the bridge, and then through the second monolith to the second conductor, and

[0094] f) the array has been produced by a process comprising the steps of:

[0095] i) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, and

[0096] ii) Joining the separate entities together by a process including a sintering or oxidation treatment step.

[0097] The array of the present invention is constructed in such a way that the electrical conductor supplied from the power source is connected at a position closest to the first end of the structured catalyst array, but the current is still directed to flow substantially from one end of the (most) individual monoliths to the opposite end through the configuration of the monolith bridge (s). This feature establishes a temperature profile in which the temperature increases from the first end to the second end of the structured catalyst. This is advantageous because it provides the possibility to connect the conductor to the cooler end of such structured catalyst, which connection is sensitive to high temperatures. In addition, this is advantageous because it allows for improved control of the chemical reaction front of the endothermic reaction promoted by the structured catalyst.

[0098] In a particular embodiment of the array of the present invention, the second conductor is directly connected to the second monolith. In this regard, the term "directly connected" means connected without an intermediate element (e.g., one or more monoliths). The connection of the conductor to the monolith can be a sintered connection or a mechanical connection, such as by welding, soldering, or brazing.

[0099] In a specific embodiment of the array of the present invention, the second conductor is indirectly electrically connected to the second monolith. In a specific embodiment of the array of the present invention, the array also includes (i) one or more parallel additional intermediate monoliths of the structured catalyst and (ii) an end monolith of the structured catalyst, wherein each additional intermediate monolith is connected to at least two parallel monoliths through a monolith bridge of a monolith bridge conductive material, and wherein the end monolith is connected to at least one parallel monolith, and wherein the second conductor is connected to the end monolith at a position located on the monolith closer to the first end than the second end. Preferably, the total number of additional intermediate monoliths and end monoliths is an even number, and the second conductor is connected to the end monolith at the first end of the array. This design allows current to flow from one end of each monolith to the opposite end. In the specific embodiment of the array of the present invention, preferably, the conductive material of the monolith bridge at the second end of the array is the same material. In the specific embodiment of the array of the present invention, preferably, the conductive material of the monolith bridge is the same material.

[0100] In a specific embodiment of the invention, where the array includes one or more intermediate monoliths, the end monolith corresponds to the second monolith of a specific embodiment, where the array includes only the first and second monoliths. In this specific embodiment of the invention, where the array includes one or more intermediate monoliths, the second conductor is connected to the end monolith instead of the second monolith.

[0101] In certain embodiments of the array of the invention, the total number of additional intermediate monoliths and end monoliths is any number from 3 to 36.

[0102] In a particular embodiment of the array of the present invention, the first and second monoliths are connected by a monolith bridge at the second end of the array, wherein each additional intermediate monolith is connected in series to two parallel monoliths by a monolith bridge of monolith bridge conductive material alternating at the first end and the second end so as to conduct current from one end of each monolith to the opposite end, and wherein the end monolith is connected to a parallel monolith at the second end.

[0103] In a particular embodiment of the array of the invention, the first and second monoliths are connected by a monolith bridge at the second end of the array.

[0104] In a particular embodiment of the array of the invention, the electrical connection between the first and second monoliths through the monolith bridge is a coherent connection, wherein in the region where the bridge is joined to the monolith by sintering or oxidation treatment, the structure of the material is the same as the structure of the adjacent material in the monolith and in the monolith bridge. Preferably, there is no distinct interface in the junction region. Alternatively, the term "coherent connection" can be defined as a consistent internal connection or a consistent coupling.

[0105] In particular embodiments of the array of the invention, the monolith bridges extend over less than 50%, preferably 40%, more preferably 30%, more preferably 20%, and most preferably 10% of the length from the first end to the second end of the first and second monoliths.

[0106] In a specific embodiment of the array of the invention, the array is produced by a method comprising the steps of:

[0107] A) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of two or three separate entities, wherein the surface areas to be connected are in a moldable state,

[0108] B) contacting the surface areas to be joined so as to form a continuous material phase in the contact area,

[0109] C) The contact areas are joined together by a process including a sintering or oxidation treatment step.

[0110] In a particular embodiment of the array of the invention, the conductive material of the monolith and the bridges of the monolith are the same material.

[0111] In a particular embodiment of the array of the invention, at least one of the conductive materials of the monolith and at least one monolith bridge is a composite of a conductive metallic material and a ceramic material. It has been found that the use of said composite material can obtain an increased resistivity compared to a material consisting only of conductive material. The increase in resistivity allows for increased heating of the material.

[0112] In a specific embodiment of the array of the present invention, the resistivity of at least one conductive material of the monolith and the monolith bridge is from 1×10E-4Ohm×m to 1×10E-7Ohm×m, preferably from 1×10E-5Ohm×m to 1×10E-7Ohm×m, more preferably from 1×10E-5Ohm×m to 5×10E-6Ohm×m, and most preferably from 5×10E-5Ohm×m to 1×10E-6Ohm×m.

[0113] In particular embodiments of the arrays of the invention, the monolithic bridge material is heat resistant up to temperatures of at least 500°C, preferably at least 700°C, preferably at least 900°C, preferably at least 1000°C, and most preferably at least 1100°C.

[0114] The endothermic reaction catalyzed by the array of the present invention can be any endothermic chemical reaction that can be catalyzed. In a specific embodiment of the array of the present invention, the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0115] In a specific embodiment of the array of the present invention, the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and the monoliths can have the same or different shapes.

[0116] In a particular embodiment of the array of the invention, the monolith has a shape such that the cross section in a plane perpendicular to the longitudinal axis is selected from a regular polygon of a triangle, rectangle, pentagon, hexagon, heptagon, octagon, nonagon, decagon, hendecagon and dodecagon. Preferably, the monolith has the same shape and such a shape that the cross section in a plane perpendicular to the longitudinal axis is selected from a triangle, rectangle and hexagon.

[0117] In a specific embodiment of the array of the present invention, the flow channel of the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and the flow channel may have the same or different shapes within a monolith and / or between different monoliths.

[0118] In a particular embodiment of the array of the invention, the flow channels of the monolith have a shape such that the cross section in a plane perpendicular to the longitudinal axis is selected from a regular polygon of a triangle, rectangle, pentagon, hexagon, heptagon, octagon, enneagon, decagon, eleven-gon and dodecagon. Preferably, the flow channels of the monolith have the same shape and such a shape that the cross section in a plane perpendicular to the longitudinal axis is selected from a triangle, rectangle and hexagon.

[0119] In certain embodiments of the array of the invention, the array is configured to generate 500 to 50,000 W / m 2 of heat flux.

[0120] In a particular embodiment of the array of the present invention, the array has an electrically insulating part, which is arranged to increase the length of the main current path between the at least two conductors to a length greater than the maximum dimension of the monolith. In a particular embodiment of the array of the present invention, the insulating part has a slit form in at least one monolith. Preferably, the slit has a longitudinal direction perpendicular to the longitudinal direction of the monolith. In a particular embodiment of the present invention, the electrically insulating part is in the form of air or a material with a high resistivity (e.g., ceramic). Preferably, the ratio of the resistivity of the conductive material of the monolith to the resistivity of the insulating part is at least 50, preferably at least 100, more preferably at least 200, more preferably at least 300, more preferably at least 400, more preferably at least 600, more preferably at least 800 and most preferably at least 1000.

[0121] In a particular embodiment of the array of the present invention, the array has at least one electrically insulating component arranged to direct current through the monolith to ensure that for at least 70% of the length of the monolith, the current density vector of the main current path has a non-zero component value parallel to the length of the structured catalyst, i.e., parallel to the longitudinal axis of the monolith. Therefore, for at least 70% of the length of the structured catalyst, the current density vector will have a positive or negative component value parallel to the length of the structured catalyst. Therefore, for at least 70% of the length of the structured catalyst, for example 90% or 95%, i.e., along the z-axis of the structured catalyst, the current density vector of the main current path will have a positive or negative value along the z-axis. This means that the current is forced to flow from the first end of the structured catalyst to the second end, and then forced to flow to the first end again. The temperature of the gas entering the first end of the structured catalyst and the endothermic steam reforming reaction occurring on the structured catalyst absorb heat from the structured catalyst. Thus, the first end of the structured catalyst remains cooler than the second end, and by ensuring that the current density vector of the main current path has a non-zero component value parallel to the length of the structured catalyst, which occurs when the temperature curve continues to rise significantly, it produces a controllable reaction front. In one embodiment, the current density vector has a non-zero component value parallel to the length of the structured catalyst in 70%, preferably 80%, more preferably 90%, and even more preferably 95% of the length of the structured catalyst. It should be noted that the term "length of the structured catalyst" is meant to represent the dimension of the structured catalyst in the direction of gas flow within the reactor unit containing the structured catalyst.

[0122] In a particular embodiment of the array of the present invention, the support member is arranged in the space between the juxtaposed monoliths, wherein no bridge is present. The purpose of the support member is to support the array structure to avoid the occurrence of breaks or cracks. In a particular embodiment of the array of the present invention, the support member is composed of a material with a high resistivity, such as a ceramic. Preferably, the ratio of the resistivity of the conductive material of the monolith to the resistivity of the material of the support member is at least 50, preferably at least 100, more preferably at least 200, more preferably at least 300, more preferably at least 400, more preferably at least 600, more preferably at least 800 and most preferably at least 1000. In a particular embodiment of the present invention, the support member extends over at least 50%, preferably at least 60%, more preferably at least 70%, more preferably at least 80% and most preferably at least 90% of the length from the first end to the second end of the monolith not occupied by the bridge.

[0123] In certain embodiments of the array of the invention, the length of the feed gas path through the array is less than the length of the current path from the first electrode through the array and to the second electrode.

[0124] In a specific embodiment of the array of the present invention, the monolithic bridge material is a material without any spaces, wherein the minimum dimension formed is 0.4 mm or greater, preferably 0.6 mm or greater, more preferably 0.8 mm or greater, more preferably 1.0 mm or greater, more preferably 1.2 mm or greater, more preferably 1.4 mm or greater, more preferably 1.6 mm or greater, more preferably 1.8 mm or greater, and most preferably 2.0 mm or greater.

[0125] In a specific embodiment of the array of the present invention, at least one monolith consists of at least two monolith parts, which are connected in series by bridge segments of bridge segment conductive material. In a specific embodiment of the array of the present invention, the one monolith consists of at least three monolith parts, preferably at least four monolith parts, more preferably at least five monolith parts, more preferably at least six monolith parts, more preferably at least seven monolith parts, and most preferably at least eight monolith parts. In a specific embodiment of the array of the present invention, the monolith parts have different resistivities. In a specific embodiment of the array of the present invention, the one monolith consists of first, second and third monolith parts positioned sequentially at least in the direction from the first end to the second end, wherein the second monolith part has a higher resistivity than the first and third monolith parts, the third monolith part has a lower resistivity than the first and second monolith parts, and the resistivity of the first monolith part is between the resistivity of the second and third composite materials. This design provides a temperature distribution from the first end to the second end of the array, which is optimized for catalysis of endothermic reactions.

[0126] Method of producing arrays

[0127] In a specific embodiment of the array of the invention, the array is produced by a method comprising the steps of:

[0128] A) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of two or three separate entities, wherein the surface areas to be connected are in a moldable state,

[0129] B) contacting the surface areas to be joined so as to form a continuous material phase in the contact area,

[0130] C) The contact areas are joined together by a process including a sintering or oxidation treatment step.

[0131] In a specific embodiment of the array of the invention, the array is produced by a method comprising the steps of:

[0132] providing a first monolithic component comprising a metal powder having a first alloy composition and a first soluble binder, the first component having a first joint surface,

[0133] Providing a second monolithic component comprising a metal powder having a second alloy composition and a second soluble binder, the second component having a second joining surface;

[0134] providing a bridge component comprising a metal powder having a third alloy composition and a third soluble binder, the bridge component having two third engagement surfaces, one at each end of the bridge component;

[0135] wherein the first alloy composition and the second and third alloy compositions each consist of a plurality of chemical elements, and wherein the chemical elements are selected such that, for each chemical element present in an amount greater than 0.5% by weight of the respective alloy composition, the chemical element is contained in both the first and second and third alloy compositions, and

[0136] - for a chemical element present in an amount of at most 5.0 wt. % in the first alloy composition, the amount of this chemical element differs by at most 1 percentage point between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand, and

[0137] - for a chemical element present in the first alloy composition in an amount greater than 5.0 wt. %, the amount of this chemical element differs by at most 3 percentage points between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand,

[0138] arranging the bridge component between the first monolithic component and the second monolithic component such that one third joint surface contacts the first joint surface and another third joint surface contacts the second joint surface,

[0139] maintaining the engaging surfaces in contact for a period of time to allow at least partial evaporation of the solvent; and

[0140] • Subsequently, the first, second and third components are sintered or oxidized together while keeping the joint surfaces in contact or as close together as possible to achieve an array.

[0141] In a specific embodiment of the above method, the following steps precede the arranging step:

[0142] The first joining surface and / or the second joining surface is at least partially dissolved by applying a solvent.

[0143] In certain embodiments of the above method, the first, second and third components are manufactured by powder extrusion, powder injection molding, additive manufacturing or tape casting.

[0144] In certain embodiments of the above methods, the metal alloy compositions of the first, second and third components include one or more of iron, chromium, aluminum, cobalt, nickel, manganese, molybdenum, vanadium, silicon or alloys thereof.

[0145] In certain embodiments of the above methods, the first, second and / or third component(s) comprise a ceramic material.

[0146] In certain embodiments of the above methods, the bridge component comprising dissolved binder and metal powder further comprises ceramic powder.

[0147] In certain embodiments of the above methods, the first binder, the second binder, and the third binder have similar or identical solubilities, for example, the first, second, and third binders are identical.

[0148] In certain embodiments of the above methods, the binder of the first, second and / or third component(s) is water soluble.

[0149] In certain embodiments of the above methods, after sintering or oxidation, the front interfaces between the first monolithic component, the second monolithic component, and the bridge component are not identifiable by analysis using a scanning electron microscope.

[0150] In certain embodiments of the above methods, a plurality of monolithic components and bridge components are joined together. In certain embodiments of the above methods, a plurality of monolithic components and bridge components are joined together to produce an array having a plurality of monoliths and bridges in a desired configuration.

[0151] Arrays with features to mitigate the adverse effects of hot spot formation

[0152] In certain embodiments of the arrays of the invention, the arrays further comprise features for mitigating adverse effects caused by hotspot formation, the features being selected from the group consisting of:

[0153] (i) arranging two monoliths connected by a monolith bridge to form a central plane, the central plane being located through the geometric centers of both monoliths and being located in the same direction as the longitudinal axis of the array, wherein the first and second monoliths have first and second widths in a direction perpendicular to the central plane, wherein the monolith bridge has a width in a direction perpendicular to the central plane, and wherein the width of the monolith bridge is greater than the first and second widths,

[0154] (ii) the monolith bridge has a larger cross-sectional area at one or both ends adjacent to the two monoliths to be connected than at the center of the bridge,

[0155] (iii) a safety bridge between the monoliths, wherein the safety bridge comprises a safety bridge conductive material having a resistance that is sufficiently high to inhibit current from flowing through the safety bridge when the monolith bridge is in operation, wherein the safety bridge is located at any point between the first and second ends of the array;

[0156] (iv) a protrusion on at least one of the first and second monoliths for connecting the first and second conductors, respectively, wherein the protrusion has a protrusion conductive material;

[0157] (v) the monolithic bridge material has a lower resistivity than the first conductive material,

[0158] (vi) The monolithic bridge includes at least a first layer and a second layer, wherein the first layer is disposed closer to the second end of the array than the second layer, and wherein the first layer has a lower resistivity than the second layer.

[0159] As described above, structured catalysts of the type of the present invention have a plurality of structural components (points) where the flow of electric current through the catalyst is restricted because the current is forced to pass through a narrow channel of reduced cross-section, such as at the second end of the structured catalyst, or to transfer from one part to another, such as from one type of material to another type of material, or across an interface between two parts. Such points are sometimes referred to as hot spots and there is a risk of overheating, which in turn leads to structural damage and partial or total loss of function. Features (i) to (vi) as defined above each mitigate the risk of hot spots forming in different structural components of the array of the present invention.

[0160] In a specific embodiment of the array of the present invention having the mitigation feature (i) as defined above, two monoliths connected by a monolith bridge have a rectangular cross-section in a plane perpendicular to the longitudinal axis and are arranged with parallel surfaces, wherein the two monoliths each have a front surface facing the other monolith, a rear surface parallel to the front surface and two side surfaces perpendicular to the front and rear surfaces, wherein the monolith bridge includes (A) a spacing portion positioned between at least a portion of the front surface, (B) one or more side portions connected to at least a portion of one or more side surfaces, and (C) a rear portion connected to at least a portion of the rear surface and connected to at least one side portion.

[0161] In a specific embodiment of the array of the present invention, the bridge has a form selected from the following: an L-shaped body, an H-shaped body, a T-shaped body, an S-shaped body, an 8-shaped body, an O-shaped body, an F-shaped body, an E-shaped body and an I-shaped body, two parallel linear bodies, and a rectangular frame body viewed in the longitudinal direction of the array, wherein the bridge has a uniform size in the longitudinal direction of the array. In a specific embodiment of the array of the present invention, each part of the body has a rectangular cross-section in a plane perpendicular to the surface of the monolith to which the part is connected. In a specific embodiment of the array of the present invention, the side parts of the bridge each have the form of an elongated linear body, whose longitudinal axis connects the side surfaces of the two monoliths to be connected, and has a rectangular cross-section in a direction perpendicular to its longitudinal direction. In a specific embodiment of the array of the present invention, the side parts extend from the rear surface of one monolith to the rear surface of the second monolith. In a specific embodiment of the array of the present invention, the elongated linear body at the surface closest to the first end of the monolith has an extension connected to the side surface of the monolith. Preferably, the extension has the form of a rectangular box from a direction perpendicular to the side surface. Alternatively, the extension has the form of a box with a triangular cross-section from a direction perpendicular to the side surface, wherein the triangle is inclined from the rear surface to the front surface.

[0162] In a specific embodiment of the array of the present invention, the side portions of the bridge each have the form of an elongated body whose longitudinal axis connects the side surfaces of the two monoliths to be connected, and, viewed from a direction perpendicular to the side surfaces, has a straight line at the edge of the side portion closest to the second end of the monolith, and a partial elliptical curve at the edge of the side portion closest to the first end of the monolith, wherein the partial elliptical curve has a descending profile in the direction from the rear surface to the front surface of the monolith.

[0163] In a particular embodiment of the array of the present invention having mitigation feature (vi) as defined above, the monolithic bridge comprises one or more intermediate layers of conductive material between the first layer and the second layer, wherein the intermediate layers have such a resistivity that the resistivity from the first layer to the second layer is at an increasing level between layers.

[0164] In a particular embodiment of the array of the invention having mitigation feature (vi) as defined above, the resistivity of the first layer is lower than the resistivity of the first conductive material and the resistivity of the second layer is higher than the first conductive material.

[0165] Endothermic reaction

[0166] In one embodiment, the endothermic reaction is the dehydrogenation of hydrocarbon compounds. The reaction is carried out according to reaction (viii). The catalyst material used for the reaction can be Pt / Al2O3 or Pt-Sn / Al2O3. The catalytically active material can be Pt. The maximum temperature of the reactor may be between 500 and 700°C. The pressure of the feed gas may be 2-5 bar.

[0167] In one embodiment, the endothermic reaction is methanol cracking. The reaction is carried out according to reactions (v), (ix) and (x). The catalyst material used for the reaction can be Ni / MgAl2O3 or Cu / Zn / Al2O3. The catalytically active material can be Cu or Ni. The maximum temperature of the reactor can be between 200 and 300°C. The pressure of the feed gas can be 2-30 bar, preferably about 25 bar.

[0168] In one embodiment, the endothermic reaction is methanol cracking. The catalyst material used for the reaction can be CuZnO / Al2O3, Fe / Al2O3NiGa / MgAl2O4 or CuZn / ZrO2. The catalytically active material can be Cu, Zn, ZnO, Fe, Ga, Ni or a combination thereof, and the ceramic coating can be Al2O3, ZrO2, MgAl2O3, CaAl2O3 or a combination thereof, and may be mixed with oxides of Y, Ti, La or Ce. The maximum temperature of the reactor can be between 150 and 1300°C. The feed pressure can be 2-200 bar, preferably about 25 bar. In one embodiment, the macrostructure is made of Fe CrAl alloy, a ceramic coating loaded with a mixture of ZrO2 and Al2O3, and CuZn as a catalytically active material. In another embodiment, the macrostructure is made of Fe CrAl alloy, a ceramic coating loaded with a mixture of ZrO2 and MgAl2O4, and Ni as a catalytically active material. In another embodiment, the macrostructure is made of FeCrAl alloy, supported by a ZrO2 ceramic coating, and Mn as a catalytically active material.

[0169] In one embodiment, the endothermic reaction is steam reforming of hydrocarbon compounds. The reaction is carried out according to reactions (i)-(v). The catalyst material used for the reaction can be Ni / Al2O3, Ni / MgAl2O3, Ni / CaAl2O3, Ru / MgAl2O3 or Rh / MgAl2O3. The catalytically active material can be Ni, Ru, Rh, Ir or a combination thereof. The maximum temperature of the reactor can be between 850 and 1300°C. The pressure of the feed gas can be 15-180 bar, preferably about 25 bar.

[0170] In one embodiment, the endothermic reaction is steam reforming of hydrocarbon compounds. The catalyst material used for the reaction can be Ni / Al2O3, Ni / ZrO2, Ni / MgAl2O3, Ni / CaAl2O3, Ru / MgAl2O3 or Rh / MgAl2O3. The catalytically active material can be Ni, Ru, Rh, Ir or a combination thereof, and the ceramic coating can be Al2O3, ZrO2, MgAl2O3, CaAl2O3 or a combination thereof, and may be mixed with oxides of Y, Ti, La or Ce. The maximum temperature of the reactor can be between 850 and 1300°C. The pressure of the feed gas can be 15-180 bar, preferably about 25 bar. In one embodiment, the macrostructure is made of FeCrAl alloy, loaded with a ceramic coating of a mixture of ZrO2 and MgAl2O4, with nickel as the catalytically active material.

[0171] In one embodiment, the endothermic reaction is ammonia cracking. The reaction is carried out according to reaction (xi). The catalyst material used for the reaction can be Fe, FeCo or Ru / Al2O3. The catalytically active material can be Fe or Ru. The maximum temperature of the reactor can be between 400 and 700°C. The pressure of the feed gas can be 2-30 bar, preferably about 25 bar.

[0172] In one embodiment, the endothermic reaction is ammonia cracking. The catalyst material used for the reaction can be Fe (prepared from Fe3O4 or FeO), FeCo, Ru / Al2O3, Ru / ZrO2, Fe / Al2O3, FeCo / Al2O3, Ru / MgAl2O3 or CoSn / Al2O3. The catalytically active material can be Ru, Rh, Fe, Co, Ir, Os or a combination thereof, and the ceramic coating can be Al2O3, ZrO2, MgAl2O3, CaAl2O3 or a combination thereof, and may be mixed with oxides of Y, Ti, La or Ce. The maximum temperature of the reactor can be between 300 and 1300°C. The pressure of the feed gas can be 2-180 bar, preferably about 25 bar. In one embodiment, the macrostructure is made of FeCrAl alloy, loaded with a ceramic coating of a mixture of ZrO2 and Al2O3, and Ru as the catalytically active material.

[0173] In one embodiment, the endothermic reaction is a synthesis of hydrogen cyanide or a synthesis of an organic nitrile. The reaction is carried out according to reactions (vi) and (vii). The catalyst material of the reaction may be Pt / Al2O3. The catalytically active material may be Pt, Co or SnCo. The maximum temperature of the reactor may be between 700 and 1200°C. The pressure of the feed gas may be 2-30 bar, preferably about 5 bar.

[0174] In one embodiment, the endothermic reaction is a synthesis of hydrogen cyanide or a synthesis process of an organic nitrile. The catalyst material used for the reaction can be Pt / Al2O3, Pt / ZrO2, Ru / Al2O3, Rh / Al2O3, Pt / MgAl2O4 or CoSn / Al2O3. The catalytically active material can be Pt, Ru, Rh, Ir, Co, Sn or a combination thereof, and the ceramic coating can be Al2O3, ZrO2, MgAl2O4, CaAl2O4 or a combination thereof, and may be mixed with oxides of Y, Ti, La or Ce. The maximum temperature of the reactor can be between 850 and 1300°C. The pressure of the feed gas can be 2-180 bar, preferably about 25 bar. In one embodiment, the macrostructure is made of Fe Cr Al alloy, loaded with a ceramic coating of a mixture of ZrO2 and Al2O3, and Pt is used as the catalytically active material.

[0175] In one embodiment, the endothermic reaction is the aromatization of hydrocarbon compounds. This favors the aromatization of higher hydrocarbon compounds.

[0176] Reactor of the present invention

[0177] The present invention also relates to a reactor system for carrying out an endothermic reaction of a raw gas, the reactor system comprising:

[0178] a) a catalyst according to the invention or an array according to the invention;

[0179] b) a pressure-resistant shell containing the catalyst, the pressure-resistant shell comprising an inlet for inputting the feed gas and an outlet for outputting the product gas, wherein the inlet is located so that the feed gas enters the catalyst at a first end and the product gas leaves the catalyst from a second end; and

[0180] c) A heat insulation layer between the structured catalyst and the pressure-resistant shell.

[0181] Use of the catalyst of the present invention

[0182] The present invention also relates to the use of a catalyst according to the invention, an array according to the invention or a reactor according to the invention, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0183] Invention Project

[0184] 1. A structured catalyst arranged to catalyze an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of an electrically conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material, wherein the electrically conductive material is at least partially a composite material in the form of a homogeneous mixture of an electrically conductive metallic material and a ceramic material, wherein the macrostructure is at least partially composed of two or more materials having different resistivities.

[0185] 2. A catalyst according to item 1, wherein the macrostructure is at least partially composed of one or more composite materials and one or more non-composite conductive metal materials.

[0186] 3. The catalyst according to any one of items 1-2, wherein the metal material is an alloy comprising one or more substances selected from Fe, Cr, Al, Co, Ni, Zr, Cu, Ti, Mn and Si.

[0187] 4. The catalyst according to any one of items 1 to 3, wherein the ceramic material is an oxide of a substance selected from Al, Mg, Ce, Zr, Ca, Y and La.

[0188] 5. The catalyst according to any one of items 1 to 4, wherein the weight ratio of the metal material to the ceramic material in the macrostructure is in the range of 50 to 1, preferably 40 to 1, more preferably 30 to 2, more preferably 24 to 3 and most preferably 19 to 4.

[0189] 6. A catalyst according to any one of items 2-5, wherein the structured catalyst is in the form of at least one monolith, wherein a plurality of flow channels are formed in the monolith for transporting the raw gas from a first end where the raw gas enters through the monolith to a second end where the product gas leaves, wherein the monolith has a longitudinal axis extending from the first end to the second end.

[0190] 7. The catalyst according to item 6, wherein the macroscopic structure of the monolith is composed of two or more composite materials with different compositions in the direction of the longitudinal axis to provide different resistivities.

[0191] 8. The catalyst according to item 7, wherein the macroscopic structure of the monolith consists of at least three composite materials, preferably at least four composite materials, more preferably at least five composite materials, more preferably at least six composite materials, more preferably at least seven composite materials, and most preferably at least eight composite materials.

[0192] 9. A catalyst according to item 8, wherein the macroscopic structure of the monolith includes at least first, second and third composite materials in the direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first and third composite materials, the third composite material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second and third composite materials.

[0193] 10. The catalyst according to item 6, wherein the macroscopic structure of the monolith is composed of one or more composite materials and non-composite conductive metal materials with different compositions in the direction of the longitudinal axis to provide different resistivities.

[0194] 11. A catalyst according to item 10, wherein the macroscopic structure of the monolith includes at least a first and a second composite material and a non-composite conductive metal material in the direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first composite material and the non-composite material, the non-composite material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second composite material and the resistivity of the non-composite material.

[0195] 12. An array comprising the first and second structured catalysts according to any one of items 1-11, wherein:

[0196] a) the first and second structured catalysts are in the form of first and second monoliths, respectively;

[0197] b) the first and second monoliths each have a plurality of flow channels formed therein for conveying the feed gas through the monolith from a first end where the feed gas enters to a second end where the product gas exits, wherein the first and second monoliths each have a longitudinal axis extending from the first end to the second end;

[0198] c) an array comprising at least first and second conductors electrically connected to the first and second monoliths, respectively, and configured to be connected to a power source, wherein the power source is dimensioned to heat at least a portion of the first and second monoliths to a temperature of at least 500° C. by passing an electric current through the macrostructure, wherein the first conductor is electrically connected directly or indirectly to the first monolith, and the second conductor is electrically connected directly or indirectly to the second monolith, and wherein the conductors are connected at a location on the array closer to the first end than to the second end,

[0199] d) the first and second monoliths are electrically connected via a monolith bridge of a monolith bridge conductive material,

[0200] e) the array is configured to direct current from the first conductor through the first monolith to the second end, then through the bridge, and then through the second monolith to the second conductor, and

[0201] f) the array has been produced by a process comprising the steps of:

[0202] i) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, and

[0203] ii) Joining the separate entities together by a process including a sintering or oxidation treatment step.

[0204] 13. The array of item 12, wherein the second conductor is directly connected to the second monolith.

[0205] 14. The array of item 13, wherein the second conductor is indirectly electrically connected to the second monolith.

[0206] 15. An array according to item 14, wherein the array further comprises (i) one or more parallel additional intermediate monoliths of structured catalyst and (ii) an end monolith of structured catalyst, wherein each additional intermediate monolith is connected to at least two parallel monoliths via a monolith bridge of monolith bridge conductive material, and wherein the end monolith is connected to at least one parallel monolith, and wherein the second conductor is connected to the end monolith at a position on the monolith closer to the first end than to the second end.

[0207] 16. The array according to item 15, wherein the total number of the additional intermediate monoliths and the end monoliths is an even number, and wherein the second conductor is connected to the end monolith at the first end of the array.

[0208] 17. An array according to item 16, wherein the first and second monoliths are connected by a monolith bridge at the second end of the array, wherein each additional intermediate monolith is connected in series to two parallel monoliths by a monolith bridge of monolith bridge conductive material alternating at the first end and the second end so as to conduct current from one end of each monolith to the opposite end, and wherein the end monolith is connected to a parallel monolith at the second end.

[0209] 18. An array according to any one of items 12-17, wherein the first and second monoliths are connected by the monolith bridge at the second end of the array.

[0210] 19. An array according to any one of items 12-18, wherein the monolith bridge extends less than 50%, preferably 40%, more preferably 30%, more preferably 20%, and most preferably 10% along the length from the first end to the second end of the first and second monoliths.

[0211] 20. An array according to any one of items 12-19, wherein the array is produced by a method comprising the steps of:

[0212] A) providing the first monolith, the second monolith or the intermediate monolith and the conductive material of the monolith bridge in the form of three separate entities, wherein the surface areas to be connected are in a moldable state,

[0213] B) contacting the surface area to be connected in a contact area,

[0214] C) The contact areas are joined together by a process including a sintering or oxidation treatment step.

[0215] 21. An array according to any one of items 12-20, wherein the array is produced by a method comprising the steps of:

[0216] providing a first monolithic component comprising a metal powder having a first alloy composition and a first soluble binder, the first component having a first joint surface,

[0217] Providing a second monolithic component comprising a metal powder having a second alloy composition and a second soluble binder, the second component having a second joining surface;

[0218] providing a bridge component comprising a metal powder having a third alloy composition and a third soluble binder, the bridge component having two third engagement surfaces, one at each end of the bridge component;

[0219] wherein the first alloy composition and the second and third alloy compositions each consist of a plurality of chemical elements, and wherein the chemical elements are selected such that, for each chemical element present in an amount greater than 0.5% by weight of the respective alloy composition, the chemical element is contained in both the first and second and third alloy compositions, and

[0220] - for a chemical element present in an amount of at most 5.0 wt. % in the first alloy composition, the amount of this chemical element differs by at most 1 percentage point between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand, and

[0221] - for a chemical element present in the first alloy composition in an amount greater than 5.0 wt. %, the amount of this chemical element differs by at most 3 percentage points between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand,

[0222] arranging the bridge component between the first monolithic component and the second monolithic component such that one third joint surface contacts the first joint surface and another third joint surface contacts the second joint surface,

[0223] maintaining the engaging surfaces in contact for a period of time to allow at least partial evaporation of the solvent; and

[0224] • Subsequently, the first, second and third components are sintered or oxidized together while keeping the joint surfaces in contact or as close together as possible to achieve an array.

[0225] 22. The array of item 21, wherein the following steps precede the arranging step:

[0226] At least partially dissolving the first joining surface and / or the second joining surface by applying a solvent.

[0227] 23. The array according to any one of items 15-22, wherein the conductive material of the monolithic bridges is the same material.

[0228] 24. The array of any one of items 15-23, wherein the conductive material of the monolithic bridges at the second end of the array is the same material.

[0229] 25. The array according to any one of items 12-24, wherein the conductive material of the monolith and the monolith bridges is the same material.

[0230] 26. The array according to any one of items 12-25, wherein at least one of the conductive materials of the monolith and the at least one monolith bridge is a composite material of a conductive metallic material and a ceramic material.

[0231] 27. An array according to any one of items 12-26, wherein the resistivity of at least one conductive material of the monolith and the monolith bridge is 1×10E-4Ohm×m to 1×10E-7Ohm×m, preferably 1×10E-5Ohm×m to 1×10E-7Ohm×m, more preferably 1×10E-5Ohm×m to 5×10E-6Ohm×m, and most preferably 5×10E-5Ohm×m to 1×10E-6Ohm×m.

[0232] 28. An array according to any one of items 12-27, wherein the monolithic bridge material is heat resistant up to a temperature of at least 500°C, preferably at least 700°C, preferably at least 900°C, preferably at least 1000°C, and most preferably at least 1100°C.

[0233] 29. An array according to any one of items 12-28, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0234] 30. An array according to any one of items 12-29, wherein the monoliths have a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and wherein the monoliths can have the same or different shapes.

[0235] 31. An array according to item 30, wherein the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is a regular polygon selected from a triangle, rectangle, pentagon, hexagon, heptagon, octagon, nonagon, decagon, undecagon and dodecagon.

[0236] 32. An array according to any one of items 12-31, wherein the array further comprises features for mitigating adverse effects caused by hot spot formation, the features being selected from:

[0237] (i) arranging two monoliths connected by the monolith bridge to form a central plane, the central plane being located through the geometric centers of both monoliths and being located parallel to the longitudinal axis of the array, wherein the first and second monoliths have first and second widths in a direction perpendicular to the central plane, wherein the monolith bridge has a width in a direction perpendicular to the central plane, and wherein the width of the monolith bridge is greater than the first and second widths,

[0238] (ii) the monolith bridge has a larger cross-sectional area at one or both ends adjacent to the two monoliths to be connected than at the center of the bridge,

[0239] (iii) a safety bridge between the monoliths, wherein the safety bridge comprises a safety bridge conductive material having a resistance that is sufficiently high to inhibit current from flowing through the safety bridge when the monolith bridge is in operation, wherein the safety bridge is located at any point between the first and second ends of the array;

[0240] (iv) a protrusion on at least one of the first and second monoliths for connecting the first and second conductors, respectively, wherein the protrusion has a protrusion conductive material;

[0241] (v) the monolithic bridge material has a lower resistivity than the first conductive material,

[0242] (vi) The monolithic bridge includes at least a first layer and a second layer, wherein the first layer is disposed closer to the second end of the array than the second layer, and wherein the first layer has a lower resistivity than the second layer.

[0243] 33. An array according to item 32(i), wherein the two monoliths connected by the monolith bridge have a rectangular cross-section in a plane perpendicular to the longitudinal axis and are arranged to have parallel surfaces, wherein the two monoliths each have a front surface facing the other monolith, a rear surface parallel to the front surface and two side surfaces perpendicular to the front and rear surfaces, wherein the monolith bridge includes (A) a spacing portion positioned between at least a portion of the front surface, (B) one or more side portions connected to at least a portion of one or more side surfaces, and (C) a rear portion connected to at least a portion of the rear surface and connected to at least one side portion.

[0244] 34. An array according to item 33, wherein the bridge has a form selected from the following: an L-shaped body, an H-shaped body, a T-shaped body, an S-shaped body, an 8-shaped body, an O-shaped body, an F-shaped body, an E-shaped body and an I-shaped body, two parallel linear bodies, and a rectangular frame body viewed in the longitudinal direction of the array, wherein the bridge has a uniform size in the longitudinal direction of the array.

[0245] 35. An array according to item 34, wherein each portion of the body has a rectangular cross-section in a plane perpendicular to the surface of the monolith to which the portion is connected.

[0246] 36. An array according to item 33, wherein the side portions of the bridge each have the form of an elongated linear body whose longitudinal axis connects the side surfaces of the two monoliths to be connected and has a rectangular cross-section in a direction perpendicular to its longitudinal direction.

[0247] 37. An array according to item 35 or 36, wherein the side portion extends from the rear surface of one monolith to the rear surface of the second monolith.

[0248] 38. An array according to any one of items 35-37, wherein the elongated linear body at the surface closest to the first end of the monolith has an extension connected to the side surface of the monolith.

[0249] 39. An array according to item 38, wherein the extension has the form of a rectangular box when viewed in a direction perpendicular to the side surface.

[0250] 40. An array according to item 39, wherein the extension has the form of a box with a triangular cross-section as seen from a direction perpendicular to the side surface, wherein the triangle is inclined from the rear surface to the front surface.

[0251] 41. An array according to item 33, wherein the side portions of the bridge each have the form of an elongated body whose longitudinal axis connects the side surfaces of the two monoliths to be connected, and, viewed from a direction perpendicular to the side surfaces, has a straight line at the edge of the side portion closest to the second end of the monolith, and a partially elliptical curve at the edge of the side portion closest to the first end of the monolith, wherein the partially elliptical curve has a descending profile in the direction from the rear surface to the front surface of the monolith.

[0252] 42. An array according to item 32(vi), wherein the monolithic bridge comprises one or more intermediate layers of conductive material located between the first layer and the second layer, wherein the intermediate layers have a resistivity such that the resistivity from the first layer to the second layer is at an increasing level between layers.

[0253] 43. An array according to item 32(vi), wherein the resistivity of the first layer is lower than the resistivity of the first conductive material, and wherein the resistivity of the second layer is higher than the first conductive material.

[0254] 44. An array according to any one of items 12-43, wherein the array is configured to generate 500 to 50,000 W / m by resistive heating of the material. 2 of heat flux.

[0255] 45. An array according to any one of items 12-44, wherein the array has an electrically insulating component arranged to increase the length of the main current path between the at least two conductors to a length greater than the maximum dimension of the monolith.

[0256] 46. ​​An array according to any one of items 12-45, wherein the array has at least one electrically insulating component arranged to direct current through the monolith to ensure that for at least 70% of the length of the monolith, the current density vector of the main current path has a non-zero component value parallel to the length of the structured catalyst.

[0257] 47. An array according to any one of items 12-46, wherein the length of the feed gas channel through the array is less than the length of the current channel from the first electrode through the array and to the second electrode.

[0258] 48. An array according to any one of items 12-47, wherein the monolithic bridge material is a material without any space, wherein the minimum dimension formed is 0.4 mm or greater, preferably 0.6 mm or greater, more preferably 0.8 mm or greater, more preferably 1.0 mm or greater, more preferably 1.2 mm or greater, more preferably 1.4 mm or greater, more preferably 1.6 mm or greater, more preferably 1.8 mm or greater, and most preferably 2.0 mm or greater.

[0259] 49. An array according to any one of items 12-48, wherein the flow channel of the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and wherein the flow channel may have the same or different shapes within a monolith and / or between different monoliths.

[0260] 50. An array according to item 49, wherein the flow channels of the monolith have a shape such that the cross-section in a plane perpendicular to the longitudinal axis is a regular polygon selected from a triangle, rectangle, pentagon, hexagon, heptagon, octagon, nonagon, decagon, hendecagon and dodecagon.

[0261] 51. A reactor system for performing an endothermic reaction of a feed gas, the reactor system comprising:

[0262] a) a catalyst according to any one of items 1 to 11 or an array according to any one of items 12 to 50;

[0263] b) a pressure vessel containing the array, the pressure vessel comprising an inlet for inputting the feed gas and an outlet for outputting the product gas, wherein the inlet is positioned so that the feed gas enters the array at a first end and the product gas leaves the array at a second end; and

[0264] c) A heat insulation layer between the structured catalyst and the pressure-resistant shell.

[0265] 52. Use of a catalyst according to any one of items 1-11 or an array according to any one of items 12-50 or a reactor system according to claim 51, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0266] Key points of the invention

[0267] 1. A structured catalyst arranged to catalyze an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure of a conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material, wherein the conductive material is a composite material in the form of a uniform mixture of a conductive metal material and a ceramic material.

[0268] 1.1. A catalyst according to point 1, wherein the conductive material is a composite material comprising different materials having different compositions, wherein one or more of the compositions comprises a metal material and a ceramic material, and wherein the different materials are positioned in such a way as to provide different resistivities in the longitudinal direction of the macroscopic structure of the monolith.

[0269] 2. The catalyst according to point 1, wherein the metal material is an alloy containing one or more substances selected from Fe, Cr, Al, Co, Ni, Zr, Cu, Ti, Mn and Si.

[0270] 3. The catalyst according to any one of points 1-2, wherein the ceramic material is an oxide of a substance selected from Al, Mg, Ce, Zr, Ca, Y and La.

[0271] 4. The catalyst according to any one of points 1 to 3, wherein the weight ratio of the metal material to the ceramic material in the macrostructure is in the range of 50 to 1, preferably 40 to 1, more preferably 30 to 2, more preferably 24 to 3 and most preferably 19 to 4.

[0272] 5. A catalyst according to any one of point 1 or points 2-4, wherein the structured catalyst is in the form of at least one monolith, wherein a plurality of flow channels are formed in the monolith for transporting the feed gas from a first end where the feed gas enters through the monolith to a second end where the product gas leaves, wherein the monolith has a longitudinal axis extending from the first end to the second end.

[0273] 6. The catalyst according to point 5, wherein the macroscopic structure of the monolith is composed of two or more composite materials having different compositions in the direction of the longitudinal axis to provide different resistivities.

[0274] 6.1 A catalyst according to any one of points 1 to 5, wherein the macrostructure of the monolith comprises more than one composite material comprising different compositions, wherein the different compositions are located in the longitudinal direction of the monolith to provide different resistivities varying along the longitudinal axis of the monolith.

[0275] 6.2. The macrostructure of the monolith according to any of the above points, which is made from a plurality of slurries having different compositions, may constitute a composite component itself produced from different materials of each slurry. In such an embodiment, the macrostructure of the monolith is a composite material comprising different materials produced from slurries having different compositions, wherein one or more slurries may have a composition different from another, and wherein the different materials are positioned in a manner to provide different resistivities in the longitudinal direction of the macrostructure of the monolith.

[0276] 6.3. In one embodiment, the macrostructure of the monolith according to any of the above points may at least partially include one or more alloys and at least partially contain one or more alloys containing ceramic particles, resulting from different compositions used to prepare multiple slurries, wherein different parts are located in the direction of the longitudinal axis, as described in the method for producing the monolith.

[0277] 7. The catalyst according to point 6, wherein the macroscopic structure of the monolith consists of at least three composite materials, preferably at least four composite materials, more preferably at least five composite materials, more preferably at least six composite materials, more preferably at least seven composite materials, and most preferably at least eight composite materials.

[0278] 8. A catalyst according to point 7, wherein the macroscopic structure of the monolith includes at least first, second and third composite materials in the direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first and third composite materials, the third composite material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the second and third composite materials.

[0279] 9. An array comprising the first and second structured catalysts according to any one of points 1 to 8, wherein:

[0280] a) the first and second structured catalysts are in the form of first and second monoliths, respectively,

[0281] b) the first and second monoliths each have a plurality of flow channels formed therein for conveying the feed gas through the monolith from a first end where the feed gas enters to a second end where the product gas exits, wherein the first and second monoliths each have a longitudinal axis extending from the first end to the second end;

[0282] c) an array comprising at least first and second conductors electrically connected to the first and second monoliths, respectively, and configured to be connected to a power source, wherein the power source is dimensioned to heat at least a portion of the first and second monoliths to a temperature of at least 500° C. by passing an electric current through the macrostructure, wherein the first conductor is electrically connected directly or indirectly to the first monolith, and the second conductor is electrically connected directly or indirectly to the second monolith, and wherein the conductors are connected at a location on the array closer to the first end than to the second end,

[0283] d) the first and second monoliths are electrically connected via a monolith bridge of a monolith bridge conductive material,

[0284] e) the array is configured to direct current from the first conductor through the first monolith to the second end, then through the bridge, and then through the second monolith to the second conductor, and

[0285] f) the array has been produced by a process comprising the steps of:

[0286] i) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, and

[0287] ii) Joining the separate entities together by a process including a sintering or oxidation treatment step.

[0288] 10. The array according to point 9, wherein the second conductor is directly connected to the second monolith.

[0289] 11. The array according to point 9, wherein the second conductor is indirectly electrically connected to the second monolith.

[0290] 12. An array according to point 10 or 11, wherein the array further comprises (i) one or more parallel additional intermediate monoliths of the structured catalyst and (ii) an end monolith of the structured catalyst, wherein each additional intermediate monolith is connected to at least two parallel monoliths via a monolith bridge of a monolith bridge conductive material, and wherein the end monolith is connected to at least one parallel monolith, and wherein the second conductor is connected to the end monolith at a position on the monolith that is closer to the first end than to the second end.

[0291] 13. An array according to item 12, wherein the total number of the additional intermediate monoliths and the end monoliths is an even number, and wherein the second conductor is connected to the end monolith at the first end of the array.

[0292] 14. An array according to point 13, wherein the first and second monoliths are connected by a monolith bridge at the second end of the array, wherein each additional intermediate monolith is connected in series to two parallel monoliths by a monolith bridge of monolith bridge conductive material alternating at the first end and the second end so as to conduct current from one end of each monolith to the opposite end, and wherein the end monolith is connected to a parallel monolith at the second end.

[0293] 15. The array according to any of points 9-14, wherein said first and second monoliths are connected by said monolith bridge at a second end of said array.

[0294] 16. An array according to any one of points 9-15, wherein the monolith bridge extends less than 50%, preferably 40%, more preferably 30%, more preferably 20%, and most preferably 10% along the length from the first end to the second end of the first and second monoliths.

[0295] 17. An array according to any one of points 9 to 16, wherein the array is produced by a method comprising the following steps:

[0296] A) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, wherein the surface areas to be connected are in a moldable state,

[0297] B) contacting the surface area to be connected in a contact area,

[0298] C) The contact areas are joined together by a process including a sintering or oxidation treatment step.

[0299] When in addition to the first and second monoliths of the array there are one or more intermediate monoliths and an end monolith, the array can still be produced by the above method, wherein in these cases the three separate entities are any two of the juxtaposed monoliths and the monolith bridge between them.

[0300] 18. An array according to any one of points 9 to 17, wherein the array is produced by a method comprising the following steps:

[0301] providing a first monolithic component comprising a metal powder having a first alloy composition and a first soluble binder, the first component having a first joint surface,

[0302] Providing a second monolithic component comprising a metal powder having a second alloy composition and a second soluble binder, the second component having a second joining surface;

[0303] providing a bridge component comprising a metal powder having a third alloy composition and a third soluble binder, the bridge component having two third engagement surfaces, one at each end of the bridge component;

[0304] wherein the first alloy composition and the second and third alloy compositions each consist of a plurality of chemical elements, and wherein the chemical elements are selected such that, for each chemical element present in an amount greater than 0.5% by weight of the respective alloy composition, the chemical element is contained in both the first and second and third alloy compositions, and

[0305] - for a chemical element present in an amount of at most 5.0 wt. % in the first alloy composition, the amount of this chemical element differs by at most 1 percentage point between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand, and

[0306] - for a chemical element present in the first alloy composition in an amount greater than 5.0 wt. %, the amount of this chemical element differs by at most 3 percentage points between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand,

[0307] arranging the bridge component between the first monolithic component and the second monolithic component such that one third joint surface contacts the first joint surface and another third joint surface contacts the second joint surface,

[0308] maintaining the engaging surfaces in contact for a period of time to allow at least partial evaporation of the solvent; and

[0309] • Subsequently, the first, second and third components are sintered or oxidized together while keeping the joint surfaces in contact or as close together as possible to achieve an array.

[0310] 19. The array according to point 18, wherein the following steps precede the arranging step:

[0311] At least partially dissolving the first joining surface and / or the second joining surface by applying a solvent.

[0312] 20. The array according to any of points 12-19, wherein the conductive material of the monolithic bridges is the same material.

[0313] 21. The array according to any of points 12-19, wherein the conductive material of the monolithic bridges at the second end of the array is the same material.

[0314] 22. The array according to any of the points 9-21, wherein the conductive material of the monolith and the monolith bridges is the same material.

[0315] 23. The array according to any of the points 9 to 22, wherein at least one of the conductive materials of the monolith and the at least one monolith bridge is a composite material of a conductive metallic material and a ceramic material.

[0316] 24. An array according to any one of items 9 to 23, wherein the resistivity of the monolith and at least one conductive material of the monolith bridge is from 1×10E-4Ohm×m to 1×10E-7Ohm×m, preferably from 1×10E-5Ohm×m to 1×10E-7Ohm×m, more preferably from 1×10E-5Ohm×m to 5×10E-6Ohm×m, and most preferably from 5×10E-5Ohm×m to 1×10E-6Ohm×m.

[0317] 25. The array according to any of points 9-24, wherein the monolithic bridge material is heat resistant up to a temperature of at least 500°C, preferably at least 700°C, preferably at least 900°C, preferably at least 1000°C, and most preferably at least 1100°C.

[0318] 26. An array according to any one of points 9-25, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0319] 27. An array according to any one of points 9-26, wherein the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and wherein the monoliths can have the same or different shapes.

[0320] 28. An array according to point 27, wherein the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is a regular polygon selected from a triangle, rectangle, pentagon, hexagon, heptagon, octagon, nonagon, decagon, hendecagon and dodecagon.

[0321] 29. The array according to any one of points 9 to 28, wherein the array further comprises features for mitigating adverse effects caused by hotspot formation, the features being selected from:

[0322] (i) arranging two monoliths connected by the monolith bridge to form a central plane, the central plane being located through the geometric centers of both monoliths and being located parallel to the longitudinal axis of the array, wherein the first and second monoliths have first and second widths in a direction perpendicular to the central plane, wherein the monolith bridge has a width in a direction perpendicular to the central plane, and wherein the width of the monolith bridge is greater than the first and second widths,

[0323] (ii) the monolith bridge has a larger cross-sectional area at one or both ends adjacent to the two monoliths to be connected than at the center of the bridge,

[0324] (iii) a safety bridge between the monoliths, wherein the safety bridge comprises a safety bridge conductive material having a resistance that is sufficiently high to inhibit current from flowing through the safety bridge when the monolith bridge is in operation, wherein the safety bridge is located at any point between the first and second ends of the array;

[0325] (iv) a protrusion on at least one of the first and second monoliths for connecting the first and second conductors, respectively, wherein the protrusion has a protrusion conductive material;

[0326] (v) the monolithic bridge material has a lower resistivity than the first conductive material,

[0327] (vi) The monolithic bridge includes at least a first layer and a second layer, wherein the first layer is disposed closer to the second end of the array than the second layer, and wherein the first layer has a lower resistivity than the second layer.

[0328] 30. An array according to point 29(i), wherein the two monoliths connected by the monolith bridge have a rectangular cross-section in a plane perpendicular to the longitudinal axis and are arranged to have parallel surfaces, wherein the two monoliths each have a front surface facing the other monolith, a rear surface parallel to the front surface and two side surfaces perpendicular to the front and rear surfaces, wherein the monolith bridge includes (A) a spacing portion positioned between at least a portion of the front surface, (B) one or more side portions connected to at least a portion of one or more side surfaces, and (C) a rear portion connected to at least a portion of the rear surface and connected to at least one side portion.

[0329] 31. An array according to point 30, wherein the bridge has a form selected from the following: an L-shaped body, an H-shaped body, a T-shaped body, an S-shaped body, an 8-shaped body, an O-shaped body, an F-shaped body, an E-shaped body and an I-shaped body, two parallel linear bodies, and a rectangular frame body viewed in the longitudinal direction of the array, wherein the bridge has a uniform size in the longitudinal direction of the array.

[0330] 32. An array according to point 31, wherein each portion of the body has a rectangular cross-section in a plane perpendicular to the surface of the monolith to which the portion is connected.

[0331] 33. An array according to point 30, wherein the side portions of the bridge each have the form of an elongated linear body whose longitudinal axis connects the side surfaces of two monoliths to be connected and has a rectangular cross-section in a direction perpendicular to its longitudinal direction.

[0332] 34. The array according to point 32 or 33, wherein the side portion extends from the rear surface of one monolith to the rear surface of the second monolith.

[0333] 35. The array according to any of points 32-34, wherein the elongated linear bodies at the surface closest to the first end of the monolith have extensions connected to the side surface of the monolith.

[0334] 36. The array according to point 35, wherein the extension has the form of a rectangular box as seen from a direction perpendicular to the side surface.

[0335] 37. An array according to point 36, wherein the extension portion has the form of a box with a triangular cross-section as seen from a direction perpendicular to the side surface, wherein the triangle is inclined from the rear surface to the front surface.

[0336] 38. An array according to point 30, wherein the side portions of the bridge each have the form of an elongated body whose longitudinal axis connects the side surfaces of the two monoliths to be connected, and, viewed from a direction perpendicular to the side surfaces, has a straight line at the edge of the side portion closest to the second end of the monolith, and a partially elliptical curve at the edge of the side portion closest to the first end of the monolith, wherein the partially elliptical curve has a descending profile in the direction from the rear surface to the front surface of the monolith.

[0337] 39. An array according to point 29(vi), wherein the monolithic bridge comprises one or more intermediate layers of conductive material located between the first layer and the second layer, wherein the intermediate layers have such a resistivity that the resistivity from the first layer to the second layer is at an increasing level between layers.

[0338] 40. The array according to point 29(vi), wherein the resistivity of the first layer is lower than the resistivity of the first conductive material, and wherein the resistivity of the second layer is higher than the first conductive material.

[0339] 41. An array according to any of points 9 to 40, wherein the array is configured to generate 500 to 50,000 W / m by resistive heating of the material. 2 of heat flux.

[0340] 42. An array according to any of points 9-41, wherein the array has electrically insulating parts arranged to increase the length of the main current path between the at least two conductors to a length greater than the maximum dimension of the monolith.

[0341] 43. An array according to any of points 9-42, wherein the array has at least one electrically insulating component arranged to direct current through the monolith to ensure that for at least 70% of the length of the monolith, the current density vector of the main current path has a non-zero component value parallel to the length of the structured catalyst.

[0342] 44. An array according to any one of points 9-43, wherein the length of the feed gas channel through the array is less than the length of the current channel from the first electrode through the array and to the second electrode.

[0343] 45. An array according to any one of points 9-44, wherein the monolithic bridge material is a material without any space, wherein the minimum dimension formed is 0.4 mm or greater, preferably 0.6 mm or greater, more preferably 0.8 mm or greater, more preferably 1.0 mm or greater, more preferably 1.2 mm or greater, more preferably 1.4 mm or greater, more preferably 1.6 mm or greater, more preferably 1.8 mm or greater, and most preferably 2.0 mm or greater.

[0344] 46. ​​An array according to any one of points 9-45, wherein the flow channel of the monolith has a shape such that the cross-section in a plane perpendicular to the longitudinal axis is selected from a polygon, a regular polygon, a circle, a semicircle, an ellipse, a semi-ellipse, a trapezoid, and wherein the flow channel may have the same or different shapes within a monolith and / or between different monoliths.

[0345] 47. An array according to point 46, wherein the flow channels of the monolith have a shape such that the cross-section in a plane perpendicular to the longitudinal axis is a regular polygon selected from a triangle, rectangle, pentagon, hexagon, heptagon, octagon, nonagon, decagon, hendecagon and dodecagon.

[0346] 48. A reactor system for performing an endothermic reaction of a feed gas, the reactor system comprising:

[0347] a) a catalyst according to any one of points 1 to 8 or an array according to any one of points 9 to 47;

[0348] b) a pressure vessel containing the array, the pressure vessel comprising an inlet for inputting the feed gas and an outlet for outputting the product gas, wherein the inlet is positioned so that the feed gas enters the array at a first end and the product gas leaves the array at a second end; and

[0349] c) A heat insulation layer between the structured catalyst and the pressure-resistant shell.

[0350] 49. Use of a catalyst according to any one of points 1 to 8, or an array according to any one of points 9 to 47, or a reactor system according to point 48, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

[0351] When a reference to a previous bullet point is returned, any sub-bullets of that bullet point are also returned.

[0352] BRIEF DESCRIPTION OF THE DRAWINGS

[0353] Figure 1 A perspective view of an array of the present invention comprising two monoliths and a monolith bridge is shown.

[0354] Figure 2 is a perspective view of an array of the present invention comprising four monoliths and three monolith bridges.

[0355] Figure 3 A perspective view of an array of the present invention comprising two monoliths, a monolith bridge and a safety bridge is shown.

[0356] Figure 4 A perspective view of an array of the present invention comprising two monoliths and a monolith bridge having 3 layers is shown.

[0357] Figure 5 A perspective view of an array of the present invention comprising two monoliths and an H-formed monolith bridge is shown.

[0358] Figure 6 A perspective view of an array of the present invention comprising two monoliths and an L-form monolith bridge is shown.

[0359] Figure 7 A perspective view of an array of the present invention comprising two monoliths and a T-shaped monolith bridge is shown.

[0360] Figure 8 A perspective view of an array of the present invention comprising three monoliths is shown.

[0361] Fig. 9 A perspective view of an array of the present invention is shown, comprising four monoliths and a monolith bridge at a second end of the array in the form of a continuous layer surrounding three sides of all four monoliths.

[0362] Fig.10 A perspective view of an array of the present invention is shown, comprising two monoliths and a monolith bridge at the second end of the array, the monolith bridge being in the form of two I-shaped boxes with triangular extensions.

[0363] Fig.11 A perspective view of an array of the present invention is shown, comprising two monoliths and a monolith bridge at the second end of the array, the monolith bridge being in the form of two I-shaped boxes with cubic extensions.

[0364] Fig.12 A perspective view of an array of the present invention is shown, comprising two monoliths and a monolith bridge at the second end of the array, the monolith bridge being in the form of two I-shaped bodies with a straight lower edge and a partially elliptical upper edge.

[0365] Fig.13 A perspective view of an array of the present invention is shown, comprising two monoliths and a monolith bridge at the second end of the array, the monolith bridge being in the form of an O-shaped box.

[0366] Fig.14 A perspective view of an array of the present invention is shown, comprising two monoliths and a monolith bridge at the second end of the array, the monolith bridge being in the form of an 8-shaped box.

[0367] FIG. 15 shows a picture of an array according to the present invention ( Fig.15A , 15B and 15D), and a diagram of the material composition of the spanning bridge ( Fig. 15C ).

[0368] Fig.16 Experimental data and operating temperatures measured during a steam reforming experiment using the array of the present invention are shown.

[0369] Fig.17 An example of the optimal geometry of the monolith in series with the monolith bridges in a structured catalyst is shown to provide 500 kW of energy to facilitate the reaction at 10 kW / m 2 An endothermic reaction with a roughly constant surface flux.

[0370] Fig.18 Experimental data showing how the resistivity ρ of the material varies as a function of the ceramic content in the form of AlO.

[0371] Detailed description of the drawings

[0372] Figure 1 An array 10 of the present invention is shown, wherein the first end 11 and the second end 12 thereof include a first monolith 13 and a second monolith 14, and a monolith bridge 15 connecting the first and second monoliths 13 and 14. The first and second monoliths 13 and 14 are in the form of a structured catalyst, which comprises a macrostructure of a conductive material, the macrostructure supporting a ceramic coating, wherein the ceramic coating supports a catalytically active material. The monolith bridge is made of a conductive material.

[0373] The first and second monoliths 13 and 14 are connected to first and second conductors (not shown) connected to an external power source (not shown). When connected to the external power source, the first and second monoliths 13 and 14 and the monolith bridge 15 can heat themselves.

[0374] The first and second monoliths 13 and 14 have flow channels formed therein, extending from the first end 11 to the second end 12 of the array 10, and are adapted to guide the feed gas through the array 10 from the first end 11 to the second end 12 to heat the feed gas while exposing it to the catalyst. The monolith bridge 15 does not have any flow channels, i.e., it is composed of a material having a continuous structure.

[0375] Figure 2 An array 20 of the present invention is shown, whose first end 21 and second end 22 include a first monolith 23, a second monolith 24, an intermediate monolith 25, an end monolith 26, a monolith bridge 27 at the second end 22 of the array between the first and second monoliths 23 and 24, a monolith bridge 28 at the first end 21 of the array between the second monolith 24 and the intermediate monolith 25, and a monolith bridge 29 at the second end 22 of the array between the intermediate monolith 25 and the end monolith 26. The monoliths 23, 24, 25 and 26 have flow channels formed therein, which extend from the first end 21 to the second end 22 of the array 20 and are suitable for guiding the raw gas through the array 20 from the first end 21 to the second end 22. The monolith bridges 27, 28 and 29 do not have any flow channels, that is, they are composed of a material having a uniform structure.

[0376] Figure 3 An array 40 of the present invention is shown, which includes a first monolith 43 and a second monolith 44 at a first end 41 and a second end 42, and a monolith bridge 45 connecting the first and second monoliths 43 and 44. The first and second monoliths 43 and 44 have flow channels 46 formed therein, which extend from the first end 41 to the second end 42 of the array 40 and are suitable for guiding the feed gas through the array 40 from the first end 41 to the second end 42. The monolith bridge 45 does not have any flow channels, that is, it is composed of a material having a uniform structure.

[0377] The array 40 also includes a safety bridge 47 of a conductive material having a resistivity that, when the monolithic bridge 45 is operative for the passage of current, is sufficiently high to prevent or strongly reduce the passage of current through the safety bridge 47. However, if the monolithic bridge 45 becomes inoperative, for example due to damage, current will pass through the safety bridge 47 to ensure continued operation of the array.

[0378] Figure 4 An array 50 of the present invention is shown, which includes a first monolith 53 and a second monolith 54 at a first end 51 and a second end 52, and a monolith bridge 55 connecting the first and second monoliths 53 and 54. The first and second monoliths 53 and 54 have flow channels formed therein, which extend from the first end 51 to the second end 52 of the array 50, and are suitable for guiding the raw gas through the array 50 from the first end 51 to the second end 52. The monolith bridge 55 does not have any flow channels, that is, it is composed of a material having a uniform structure.

[0379] The monolith bridge 55 is composed of three layers of conductive material, including a first layer 56, an intermediate layer 57, and a second layer 58. The conductivity of the first layer 56 is higher than the conductivity of the first and second monoliths 53 and 54. The conductivity of the intermediate layer 57 is lower than the conductivity of the first and second monoliths 53 and 54. The conductivity of the second layer 58 is lower than the conductivity of the intermediate layer 57. The conductivity levels in the three layers 56, 57, and 58 are selected so that the current flowing from the first monolith to the second monolith is roughly evenly distributed among the three layers.

[0380] To further help achieve such uniform current distribution among the three layers 56 , 57 , and 58 , the thickness of layer 56 is greater than the thickness of layer 57 , and the thickness of layer 57 is greater than the thickness of layer 58 .

[0381] This configuration of the monolithic bridge ensures that the current density in the monolithic bridge is relatively low, thereby reducing the risk of hot spots.

[0382] Figure 5 An array 60 of the present invention is shown, which includes a first monolith 63 and a second monolith 64 at a first end 61 and a second end 62, and a monolith bridge 65 connecting the first and second monoliths 63 and 64. The first and second monoliths 63 and 64 have flow channels 66 formed therein, which extend from the first end 61 to the second end 62 of the array 60 and are suitable for guiding the feed gas through the array 60 from the first end 61 to the second end 62. The monolith bridge 65 does not have any flow channels, that is, it is composed of a material having a uniform structure.

[0383] The first and second monoliths 63 and 64 have a quadratic cross section and are arranged to have parallel surfaces. The monolith bridge 65 is composed of a bridge in the form of an H-shaped box including a spacer portion 67 having a square cross section disposed between two front faces 68 and 69 of the first and second monoliths 63 and 64 facing each other, and two linear portions 70 and 71 having a square cross section, wherein the portion 70 is connected to side surfaces 72 and 73 on one side of the monoliths 63 and 64 and to the side of the spacer portion 67, and wherein the portion 71 is connected to side surfaces 74 and 75 on the opposite sides of the monoliths 63 and 64 and to the side of the spacer portion 67.

[0384] The current flowing from the first monolith 63 to the second monolith 64 will flow partly through the spaced portion 67 and partly through the linear portions 70 and 71. The H-shaped bridge thus provides an increased cross-section for the current to flow through, thereby reducing the current density and reducing the heating of the bridge, which in turn reduces the risk of hot spots occurring.

[0385] Figure 6 An array 80 is shown, including a first monolith 81 and a second monolith 82, and a monolith bridge 83 connecting the first and second monoliths 81 and 82. The first and second monoliths 81 and 82 have a square cross section and are arranged to have parallel surfaces. The monolith bridge 83 is composed of a bridge in the form of an L-shaped box, the L-shaped box including a spacing portion 84 with a square cross section disposed between two front faces 85 and 86 of the first and second monoliths 81 and 82 facing each other, and a linear portion 87 with a square cross section, wherein the portion 87 is connected to a side 88 on one side of the monolith 82, and to a side of the spacing portion 84.

[0386] The current flowing out of the first monolith 81 will flow partly through the spacer portion 84 directly into the second monolith 82, and partly through the spacer portion 84 into the linear portion 87 and then into the second monolith 82. Thus, the L-shaped bridge provides an increased cross-section for the current to flow through, thereby reducing the current density and reducing the heating of the bridge, which in turn reduces the risk of hot spots.

[0387] Figure 7 An array 90 is shown, including a first monolith 91 and a second monolith 92, and a monolith bridge 93 connecting the first and second monoliths 91 and 92. The first and second monoliths 91 and 92 have a square cross section and are arranged to have parallel surfaces. The monolith bridge 93 is composed of a bridge in the form of a T-box, the T-box including a spacing portion 94 with a square cross section disposed between two front faces 95 and 96 of the first and second monoliths 91 and 92 facing each other, and one linear portion 97 with a square cross section, wherein the portion 97 is connected to two side faces 98 and 99 on one side of the monoliths 91 and 92, and to the side of the spacing portion 94.

[0388] The current flowing from the first monolith 91 to the second monolith 92 will flow partly through the spaced portions 94 and partly through the linear portions 97. The T-bridge thus provides an increased cross-section for the current to flow through, thereby reducing the current density and reducing heating of the bridge, which in turn reduces the risk of hot spots occurring.

[0389] Figure 8 An array 110 having a first end 111 and a second end 112 is shown, which includes a first monolith 113, a second monolith 114, and an end monolith 115. The first monolith 113 is connected to the second monolith 114 via a monolith bridge 116 at the second end of the array. The second monolith 114 is connected to the end monolith 115 via a monolith bridge 117 at the first end of the array. A first conductor 118 is connected to the first end 111 of the first monolith 113, and a second conductor 119 is connected to the first end 111 of the end monolith 115. In this embodiment, the end monolith is heated by a gas passing therethrough.

[0390] Fig. 9 An array 120 is shown, which includes two first monoliths 123 and 124 and two end monoliths 125 and 126 at a first end 121 and a second end 122. All four monoliths are connected at the second end by a monolith bridge 127 in the form of a layer surrounding three sides of all four monoliths. First conductors 128 and 129 are connected to the first ends 121 of the first monoliths 123 and 124, and second conductors 130 and 131 are connected to the first ends 121 of the end monoliths 125 and 126.

[0391] The current is directed to the first monolith 123 through the conductor 128 and reaches the end monoliths 125 and 126 through the bridge 127. Similarly, the current is directed to the first monolith 124 through the conductor 129 and reaches the end monoliths 125 and 126 through the bridge 127. This structure can be called parallel coupling. An advantage of the array 120 is that if one of the units consisting of the conductor and the monolith becomes defective during use, thereby preventing current from flowing therethrough, the array will continue to operate and the operation of the reactor using the array for the endothermic reaction will not be interrupted. In addition, the advantage of the parallel coupling of the array 120 is that it can handle a 3-phase energy supply.

[0392] Fig.10An array 140 is shown, including a first monolith 141 and a second monolith 142, and a monolith bridge 143 connecting the first and second monoliths 141 and 142. The first and second monoliths 141 and 142 have a square cross section and are arranged to have parallel surfaces. The monolith bridge 143 is in the form of two box-shaped linear portions 144 and 145, having a square cross section, wherein the portion 144 on one side of the monoliths 141 and 142 is connected to two side surfaces 146 and 147 of the monoliths 141 and 142, and wherein the portion 145 on the opposite side of the monoliths 141 and 142 is connected to two side surfaces 148 and 149 of the monoliths 141 and 142.

[0393] The linear portion 144 includes extensions 150 and 151 located at the end closest to the first end of the array 140. The linear portion 145 includes extensions 152 and 153 located at the end closest to the first end of the array 140. The extensions 150-153 have the form of a box having a triangular cross-section as viewed in a direction perpendicular to the side, wherein the triangle is inclined from the rear surface of the monoliths 141 and 142 to the front surface thereof.

[0394] The current flowing from the first monolith 141 to the second monolith 142 will flow partly through the linear portions 144 and 145 and partly through the triangular extensions. Thus, the bridge 143 provides an increased cross-sectional area for the current flow, thereby reducing the resistivity and heating of the bridge, which in turn reduces the risk of hot spots. Furthermore, due to the fact that the cross-sectional area of ​​the extensions 150-153 increases towards the back of the monolith, the current is distributed over the entire extension on the side of the monolith. Thus, with this design, the risk of hot spots is even further reduced.

[0395] Fig.11 An array 160 is shown, including a first monolith 161 and a second monolith 162, and a monolith bridge 163 connecting the first and second monoliths 161 and 162. The first and second monoliths 161 and 162 have a square cross section and are arranged to have parallel surfaces. The monolith bridge 163 is in the form of two box-shaped linear portions 164 and 165, having a square cross section, wherein the portion 164 on one side of the monoliths 161 and 162 is connected to two side surfaces 166 and 167 of the monoliths 161 and 162, and wherein the portion 165 on the opposite side of the monoliths 161 and 162 is connected to two side surfaces 168 and 169 of the monoliths 161 and 162.

[0396] Linear portion 164 includes extensions 170 and 171 at its end closest to the first end of array 160. Linear portion 165 includes extensions 172 and 173 at its end closest to the first end of array 160. Extensions 170-173 have the form of a box having a square cross-section when viewed in a direction perpendicular to the side.

[0397] The design of Bridge 163 reduces the risk of hot spots for the same reasons as Fig.10 Same as described.

[0398] Fig.12 An array 180 is shown, including a first monolith 181 and a second monolith 182, and a monolith bridge connecting the first and second monoliths 181 and 182. The first and second monoliths 181 and 182 have a square cross section and are arranged to have parallel surfaces. The monolith bridge includes a spacer portion 183 having a rectangular cross section, the spacer portion 183 being disposed between two front faces 184 and 185 of the first and second monoliths 181 and 182, and two elongated side portions 186 and 187 having a square cross section, wherein the portion 186 is connected to the side faces 188 and 189 on one side of the monoliths 181 and 182, but not connected to the side of the spacer portion 183, and wherein the portion 187 is connected to the side faces 190 and 191 on the opposite sides of the monoliths 181 and 182, but not connected to the side of the spacer portion 183.

[0399] The side portions 186 and 187 each have the form of an elongated body, the longitudinal axis of which connects the side surfaces of the two monoliths to be connected, and, viewed perpendicularly to the side surfaces, have the form of a straight line at the edge of the side portion closest to the second end of the monolith, and a curve in the form of a partial ellipse at the edge of the side portion closest to the first end of the monolith, wherein the curve in the form of a partial ellipse has a descending profile in the direction from the rear surface to the front surface of the monolith. This design allows for better current distribution, thereby reducing the risk of hot spot formation.

[0400] Fig.13 An array 200 is shown, comprising a first monolith 201 and a second monolith 202, and a monolith bridge 203 connecting the first and second monoliths 201 and 202. The first and second monoliths 201 and 202 have a square cross-section and are arranged to have parallel surfaces. The monolith bridge 203 has the form of a box-shaped rectangular frame with a rectangular cross-section, wherein the frame is connected to the sides and back of the monolith bridges 201 and 202. This design allows for better current distribution, thereby reducing the risk of hot spot formation.

[0401] Fig.14 Shows the Fig.13 The structure of the array 210 shown is the same as that of the array, except that in addition to the box-shaped rectangular frame 211, the integral bridge also includes a spacing portion 212 arranged between the two front surfaces 213 and 214 of the first and second integral bodies 215 and 216. The sides of the spacing portion 212 are connected to the sides of the frame. This design allows even better current distribution, thereby reducing the risk of hot spot formation. Example

[0402] Example 1: Photo analysis and structural performance testing of the array of the present invention

[0403] Figure 15 shows an example of an array according to the present invention, where two monoliths of 10 channels are connected with a monolith bridge. The length of the monolith is 12 cm and the rectangular cross-section dimensions are 1.5 x 3.0 cm. The monolith bridge is 1.3 cm long between the monoliths and is connected to the monoliths with a contact area of ​​1.0 x 3.0 cm.

[0404] All three entities are made from the same metal powder material of FeCr alloy. Analysis of the bridge by scanning electron microscopy and energy dispersive X-ray spectroscopy revealed:

[0405] 1. Since there is no obvious separation or interface between the connected parts in the SEM images, it is impossible to visually distinguish the bridge from the monolith, see Fig.15A , 15B and 15D. The only distinguishing feature between the three entities is the slightly higher porosity in the monolith compared to the bridge material, resulting in a higher proportion of voids in the monolith.

[0406] 2. Monolithic bridge The material composition of the monolithic part is difficult to distinguish, see Fig. 15C , since the same metal powder material was used, as shown by line scan analysis. In addition, the graphs confirm that there is no significant difference in the material composition in the interface between the connected parts compared to the composition in the monolith and the bridge. Fig. 15C The signal dips in the graph are the result of scanning through the voids in the material.

[0407] Example 2: Experimental data and operating temperatures measured during a steam reforming experiment using the array of the present invention

[0408] Fig.16The experimental data and operating temperature measured during the steam reforming reaction experiment in the array according to the present invention are shown, wherein 4 monoliths with external dimensions of 12 cm (length) x1 cm x 1 cm are connected to the monolith bridge with a length of 1.3 mm between the monoliths at the alternating ends. The AC power supply is connected to the uppermost 1 cm of the first end of the first monolith and the uppermost 1 cm of the first end of the fourth monolith. In the experiment, at a feed temperature of 251 ° C and a pressure of 9 barg, a feed of 32% CH4, 2% H2 and 66% H2O with a total feed flow rate of 100 Nl / h was fed to the reactor system of the present invention, wherein the feed temperature corresponds to the temperature of the first end of the array. The data show that the temperature measured near the second end of the monolith is a function of the energy flux into the feed gas. This illustrates how this embodiment of the array of the present invention can withstand a temperature of at least 1180 ° C without experiencing any mechanical failure in the experiment. In addition, the data show that the present invention allows an electrically heated array with a significant temperature distribution over the length of the array, wherein in a given case, the temperature increases by about 900 ° C from the first end to the second end. One advantage of the present invention is having relatively cool ends to handle electrical connection to the electrical conductors of a connected power source while still achieving high outlet temperatures to promote high temperature endothermic reactions.

[0409] Example 3: Optimal geometry of monoliths connected in series with monolith bridges

[0410] Fig.17 An example of the optimal geometry of monoliths connected in series with monolith bridges in an array of the present invention is shown for providing 500 kW of energy to be used at 10 kW / m using a circuit of 800 A and 625 V. 2 The endothermic reaction is promoted at a substantially constant surface flux of . The monolith has square channels of approximately 0.25 cm x 0.25 cm, walls of 0.44 mm thickness and 0.5 m length. The examples illustrate the desired cross-section of the monolith as a function of the actual resistance. A number of arrays were tested, which obtained different resistivities by using different material compositions in the form of composites of metallic and ceramic materials.

[0411] The experiments show that by using a higher resistance monolith obtained by using a composite material, a larger monolith cross section can be used, which offers the possibility of reducing the number of monoliths required. This in turn reduces the number of monolith bridges required and therefore reduces the number of connections required to build the array of the invention. Overall, the diagram illustrates how the concepts of the invention regarding connecting monoliths and regarding the selection of materials with different resistivities together enable the production of monolith arrays with improved performance.

[0412] Embodiment 4:

[0413] Fig.18The results obtained during the development of the invention are shown. It shows how the resistivity p of the material varies as a function of the ceramic content in the form of AlO. The figure is based on experiments in which the resistivity of a composite assembly used in the catalyst of the invention as described above was measured. The resistivity was measured by applying a known current to the assembly and measuring the voltage drop with two probes arranged in contact with the assembly, with a fixed distance between the two probes. The experiments were carried out at room temperature and at a higher temperature, both showing different resistivities.

[0414] Experiments have shown that it is possible to prepare composite materials of conductive metal materials and ceramic materials having a selected resistivity within a wide range.

Claims

1. A structured catalyst arranged for catalyzing an endothermic reaction of a feed gas, the structured catalyst comprising a macrostructure composed of an electrically conductive material, the macrostructure carrying a ceramic coating, wherein the ceramic coating carries a catalytically active material, wherein the electrically conductive material is at least partially a composite material in the form of a homogeneous mixture of an electrically conductive metallic material and a ceramic material, wherein the macrostructure is at least partially composed of two or more materials having different resistivities, The structured catalyst is in the form of at least one monolith, wherein a plurality of flow channels are formed in the monolith for transporting the feed gas from a first end where the feed gas enters to a second end where the product gas leaves through the monolith, wherein: The monolith has a longitudinal axis extending from the first end to the second end; and The macroscopic structure of the monolith is composed of two or more composite materials with different compositions in the direction of the longitudinal axis to provide different resistivities.

2. The catalyst according to claim 1, wherein the macrostructure is at least partially composed of one or more composite materials and one or more non-composite conductive metal materials, wherein the non-composite conductive metal material is a conductive metal material that does not contain a ceramic material.

3. The catalyst according to claim 1 or 2, wherein the conductive metal material is an alloy comprising one or more substances selected from Fe, Cr, Al, Co, Ni, Zr, Cu, Ti, Mn and Si.

4. The catalyst according to claim 1 or 2, wherein the ceramic material is an oxide of a substance selected from the group consisting of Al, Mg, Ce, Zr, Ca, Y and La.

5. The catalyst according to claim 1 or 2, wherein the ratio based on the weight of the conductive metal material to the ceramic material in the macrostructure is in the range of 50 to 1.

6. The catalyst according to claim 1 or 2, wherein the ratio based on the weight of the conductive metal material to the ceramic material in the macrostructure is in the range of 40 to 1.

7. The catalyst according to claim 1 or 2, wherein the ratio based on the weight of the conductive metal material to the ceramic material in the macrostructure is in the range of 30 to 2.

8. The catalyst according to claim 1 or 2, wherein the ratio of the conductive metal material to the ceramic material based on the weight in the macrostructure is in the range of 24 to 3.

9. The catalyst according to claim 1 or 2, wherein the ratio of the conductive metal material to the ceramic material based on the weight in the macrostructure is in the range of 19 to 4.

10. The catalyst of claim 1, wherein the macrostructure of the monolith consists of at least three composite materials.

11. The catalyst according to claim 1, wherein the macrostructure of the monolith consists of at least four composite materials.

12. The catalyst of claim 1, wherein the macrostructure of the monolith consists of at least five composite materials.

13. The catalyst of claim 1, wherein the macrostructure of the monolith consists of at least six composite materials.

14. The catalyst of claim 1, wherein the macrostructure of the monolith consists of at least seven composite materials.

15. The catalyst of claim 1, wherein the macrostructure of the monolith consists of at least eight composite materials.

16. The catalyst according to any one of claims 10-15, wherein the macrostructure of the monolith comprises at least first, second and third composite materials in the direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first and third composite materials, the third composite material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second and third composite materials.

17. The catalyst according to claim 1, wherein the macrostructure of the monolith is composed of one or more composite materials having different compositions and one non-composite conductive metal material in the direction of the longitudinal axis to provide different resistivities.

18. The catalyst of claim 17, wherein the macrostructure of the monolith comprises at least first and second composite materials and a non-composite conductive metal material in a direction from the first end to the second end, wherein the second composite material has a higher resistivity than the first composite material and the non-composite conductive metal material, the non-composite conductive metal material has a lower resistivity than the first and second composite materials, and the resistivity of the first composite material is between the resistivity of the second composite material and the resistivity of the non-composite conductive metal material.

19. An array comprising two catalysts according to any one of claims 1 to 18, the two catalysts being a first and a second structured catalyst, wherein: a) the first and second structured catalysts are in the form of first and second monoliths, respectively; b) the first and second monoliths each have a plurality of flow channels formed therein for conveying the feed gas through the monolith from a first end where the feed gas enters to a second end where the product gas exits, wherein the first and second monoliths each have a longitudinal axis extending from the first end to the second end; c) an array comprising at least first and second conductors electrically connected to the first and second monoliths, respectively, and configured to be connected to a power source, wherein the power source is dimensioned to heat at least a portion of the first and second monoliths to a temperature of at least 500° C. by passing an electric current through the macrostructure of the monolith, wherein the first conductor is electrically connected directly or indirectly to the first monolith, and the second conductor is electrically connected directly or indirectly to the second monolith, and wherein the first and second conductors are connected at a location on the array closer to the first end than to the second end, d) the first and second monoliths are electrically connected via a monolith bridge composed of a monolith bridge conductive material, e) the array is configured to direct current from the first conductor through the first monolith to the second end, then through the monolith bridge, and then through the second monolith to the second conductor, and f) the array has been produced by a process comprising the steps of: i) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, and ii) Joining the separate entities together by a process including a sintering or oxidation treatment step.

20. The array of claim 19, wherein the second conductor is indirectly electrically connected to the second monolith.

21. The array of claim 20, wherein the array further comprises (i) one or more juxtaposed additional intermediate monoliths of the structured catalyst and (ii) an end monolith of the structured catalyst, wherein each additional intermediate monolith is connected to at least two juxtaposed monoliths via a monolith bridge comprised of a monolith bridge conductive material, and wherein the end monolith is connected to at least one juxtaposed monolith, and wherein a second conductor is connected to the end monolith at a location on the monolith closer to the first end than to the second end, in, The first and second monoliths are connected at a second end of the array by a monolith bridge, and wherein each additional intermediate monolith is connected in series to two parallel monoliths via monolith bridges composed of monolith bridge conductive material alternating at the first end and the second end so as to conduct current from one end of each monolith to the opposite end, and wherein the end monolith is connected to one parallel monolith at the second end.

22. An array according to any one of claims 19 to 21, wherein the array is produced by a method comprising the steps of: A) providing the first monolith, the second monolith and the conductive material of the monolith bridge in the form of three separate entities, wherein the surface areas to be connected are in a moldable state, B) contacting the surface area to be connected in a contact area, C) The contact areas are joined together by a process including a sintering or oxidation treatment step.

23. An array according to any one of claims 19 to 21, wherein the array is produced by a method comprising the steps of: providing a first monolithic component comprising a metal powder having a first alloy composition and a first soluble binder, the first component having a first joining surface, ● providing a second monolithic component comprising a metal powder having a second alloy composition and a second soluble binder, the second component having a second joining surface; ● providing a monolithic bridge comprising a metal powder having a third alloy composition and a third soluble binder, the monolithic bridge having two third bonding surfaces, one at each end of the monolithic bridge; wherein the first alloy composition and the second and third alloy compositions each consist of a plurality of chemical elements, and wherein the chemical elements are selected such that, for each chemical element present in an amount greater than 0.5 weight percent of the respective alloy composition, the chemical element is contained in both the first and second and third alloy compositions, and - for a chemical element present in an amount of at most 5.0 wt. % in the first alloy composition, the amount of this chemical element differs by at most 1 percentage point between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand, and - for a chemical element present in the first alloy composition in an amount greater than 5.0 wt. %, the amount of this chemical element differs by at most 3 percentage points between the first alloy composition on the one hand and each of the second and third alloy compositions on the other hand, • arranging the monolithic bridge between the first monolithic component and the second monolithic component such that one third joint surface contacts the first joint surface and another third joint surface contacts the second joint surface, - maintaining the engaging surfaces in contact for a period of time to allow at least partial evaporation of the solvent; and Subsequently, the first, second and third components are sintered or oxidized together while keeping the joint surfaces in contact or as close together as possible to achieve an array.

24. The array of claim 23, wherein the arranging step is preceded by: • At least partially dissolving the first joining surface and / or the second joining surface by applying a solvent.

25. A reactor system for carrying out an endothermic reaction of a feed gas, the reactor system comprising: a) a catalyst according to any one of claims 1 to 18 or an array according to any one of claims 19 to 24; b) a pressure-resistant shell containing the catalyst, the pressure-resistant shell comprising an inlet for inputting the feed gas and an outlet for outputting the product gas, wherein the inlet is located so that the feed gas enters the catalyst at a first end and the product gas leaves the catalyst from a second end; and c) A heat insulation layer between the structured catalyst and the pressure-resistant shell.

26. Use of the catalyst according to any one of claims 1-18, the array according to any one of claims 19-24, or the reactor system according to claim 25, wherein the endothermic reaction is selected from steam methane reforming, hydrogen cyanide production, methanol cracking, ammonia cracking, reverse water gas shift and dehydrogenation.

Citation Information

Patent Citations

  • Allothermal methane reforming with physical energy recovery

    DE102013226126A1

  • Conductive honeycomb structures for electrically heatable automotive catalytic converters

    JP2709302B2

  • A plant and process for producing synthesis gas

    WO2019110268A1